High cycle life lithium ion battery cell with nanostructured silicon-containing anode

By designing columnar structures and voids in the silicon anode of the lithium-ion battery cell, the rupture problem caused by volume changes in the silicon anode in the lithium-ion battery cell is solved, and the specific capacity and cycling stability of the battery are improved.

CN119487646APending Publication Date: 2025-02-18LEYDENJAR TECH BV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380051897.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-04
Filing Date
2023-07-04
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The anisotropic stress caused by volume changes in the charge and discharge cycle of the lithium-ion battery cell causes the silicon material to break, break or delaminate, reducing the charging capacity and cycle life.

Method used

A silicon layer with multiple columnar structures is used to form a silicon layer on the current collector layer, combining native and secondary void structures to reduce internal stress and maintain a high surface area to adapt to the expansion of lithium.

Benefits of technology

It improves the specific capacity and charging cycle stability of lithium-ion battery cells, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005227937220000011
    Figure HDA0005227937220000011
  • Figure HDA0005227937220000021
    Figure HDA0005227937220000021
  • Figure HDA0005227937220000031
    Figure HDA0005227937220000031
Patent Text Reader

Abstract

The present application relates to a lithium ion battery cell comprising: a silicon anode; a cathode; a separator; and an electrolyte, the silicon anode including: a current collector layer and a silicon layer, in which the silicon layer includes a plurality of columnar structures on the current collector, the electrolyte including: 9 wt.% to 29 wt.% of a lithium salt with respect to the electrolyte; a non-aqueous solvent; and a diluent, where the electrolyte has a lithium salt-solvent-diluent molar ratio of 1: x: y, where 1.0 < = x < = 3 and 2.0 < = y < = 4.0.
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The present invention relates to a lithium-ion battery cell and a battery of such a battery cell, wherein the lithium-ion battery cell comprises: (i) a silicon anode, the silicon anode comprising a silicon layer; the silicon layer comprising a plurality of columnar structures on a current collector; and (ii) an electrolyte, the electrolyte comprising a lithium salt, a non-aqueous solvent and a diluent. Background of the Invention

[0003] A battery is a device consisting of one or more electrochemical cells with external connections that convert stored chemical energy into electrical energy. A battery cell has a positive and a negative electrode, also known as the cathode and anode, respectively. When the battery is connected to an external circuit, electrons flow from the anode to the cathode through the external circuit, thereby delivering electrical energy to the circuit and any devices connected to the circuit.

[0004] Primary batteries, such as alkaline batteries, are disposable because the electrode materials are permanently changed during discharge. Secondary batteries, such as lithium-ion batteries, can be charged and discharged many times because the original composition of the electrode materials can be restored by applying a reverse current.

[0005] A battery cell consists of two half-cells connected in series via a conductive electrolyte material.

[0006] One of the half-cells contains a cathode and the other half-cell contains an anode, and an electrolyte is present in both half-cells. A separator may be present between the two half-cells. The separator prevents a short circuit between the cathode and the anode while still allowing ions to move across the separator between the two half-cells.

[0007] A particularly advantageous type of electrochemical cell is a lithium-ion cell. In a lithium-ion cell, lithium ions move from the negative electrode or anode through the electrolyte to the positive electrode or cathode during discharge and back during charging. Lithium-ion cells have historically employed lithium intercalation compounds at the positive electrode and graphite at the negative electrode. Lithium-ion cells generally have a higher energy density than conventional lead-acid batteries, advantageously have no memory effect and generally exhibit low self-discharge. Examples of electrolytes that can be used for lithium-ion cells are disclosed, for example, in US-A-2018254524.

[0008] Recent developments in lithium-ion battery cells have sought to use silicon in the anode material instead of the historically used graphite. This is because silicon allows for much higher maximum capacities than the approximately 370 mAh / g that can be achieved with graphite. For example, pristine silicon allows for a specific capacity of approximately 3600 mAh / g. Achieving higher charge capacities without significantly increasing weight is a key challenge for improving the battery life of mobile phones, drones or electric cars.

[0009] One factor slowing the widespread commercialization of lithium-ion battery cells with silicon-containing anodes is that silicon typically exhibits a large volume change upon lithium insertion, wherein the volume may increase by as much as 300% to 400%. This volume change typically induces large anisotropic stresses within the anode, which may cause the silicon material of the anode to crack, break, or delaminate. Cracking, breaking, or delamination of the silicon material of the anode reduces the charge capacity of the anode and reduces the charge cycle life of a battery cell containing such an anode.

[0010] To overcome these swelling problems, a range of three-dimensional silicon surface morphologies for anodes have been developed. One approach is to develop so-called nanostructured architectures, examples of which include three-dimensional thin films, nanowires, and nanotubes. Three-dimensional thin film silicon anodes adopt a geometry that is most similar to traditional thin film batteries, in which a thin film of silicon is deposited on a metal foil, where the metal foil is used as a current collector. Thin film "two-dimensional" batteries are typically limited to a film depth between 2 microns and 5 microns to avoid cracking, fragmentation, and / or delamination of the silicon layer, thereby limiting the areal capacity to a significantly smaller area capacity than that obtainable by a three-dimensional thin film. Three-dimensional thin films use a third dimension corresponding to depth to increase the electrochemically active area. Examples of such battery cells are disclosed, for example, in US-A-2007031744.

[0011] One option for doing this is to etch perforations into the silicon film by inductively coupled plasma etching on the silicon. Another option is to deposit silicon by plasma enhanced chemical vapor deposition, so that a thin film of silicon is deposited on a metal collector foil, wherein the film is primarily formed by silicon pillars extending perpendicular to the surface of the metal foil. Such pillars typically have a diameter of several hundred nanometers. Between the pillars but also within the pillars is a network of voids or empty spaces. These nanostructured surface morphologies allow the pillars to swell, i.e., increase in volume, thereby extending into the voids. This means that when swelling, one pillar exerts little or no pressure on an adjacent pillar, which means that overall, the bulk silicon material exerts little or no pressure parallel to the surface of the metal foil. This advantageously allows these materials with nanostructured surface morphologies to avoid cracking, breaking or delamination.

[0012] A different strategy is to construct silicon in the form of nanostructures (such as nanoparticles, nanowires, nanotubes or more complex 3D structures). Through these nanostructures, silicon has ample space to accommodate volume expansion, reduce internal stress and fracture, while also maintaining a high surface area for lithium ions to be transferred from the electrolyte to the silicon. For example, WO2010129910A2 discloses a conductive substrate and a silicon-containing nanowire substrate fixed to the conductive substrate. WO2015175509A1 extends this concept by having two layers of silicon material coated with a nanowire template fixed to a substrate, wherein the second silicon layer has a higher density than the first layer. WO2015175509A1 points out that the first silicon layer thus provides space into which silicon can expand when absorbing lithium, while the second silicon layer reduces the formation of the SEI layer.

[0013] One such example is silicon nanowires grown on a rigid current collector substrate by a gas-liquid-solid process. The wires are attached to the current collector material at one end, and the irregular network of silicon wires is believed to allow for accommodation of large strains due to swelling caused by the incorporation of lithium. This advantageously allows these materials with nanostructured surface morphology to avoid cracking, fragmentation, or delamination.

[0014] In general, these silicon-containing anodes with three-dimensional morphology have a relatively high surface area of ​​the anode in contact with the electrolyte. This is advantageous in one aspect because they reduce the local current density.

[0015] During the first charge-discharge cycle of a lithium-ion battery cell operation, the electrolyte decomposes to form a series of generally ill-defined lithium-containing compounds on the surface of the anode, producing a layer called the solid-electrolyte interface (SEI). The solid-electrolyte interface layer is the result of the reduction potential of the anode. During charging, lowering the potential at the anode results in electrochemical reduction of some components of the electrolyte at the surface. Since the SEI layer is formed in part by lithium-containing compounds, the generation of SEI growth reduces the overall charge capacity of the battery cell by consuming some of the lithium that would otherwise be available for storing charge. This is a degradation mechanism known as lithium inventory loss (LLI). The properties and evolution of the solid-electrolyte interface layer fundamentally affect the overall performance of the lithium-ion battery cell. Reasons for this include: (i) the permeability (impermeability) of the solid-electrolyte interface layer to lithium ions can limit the rate and / or amount of lithium that can be stored at the anode; and (ii) the resistivity of the solid-electrolyte interface layer affects the rate of growth of the solid-electrolyte interface layer. Generally, the more conductive the SEI layer formed, the faster the further electrolyte decomposition and therefore the faster the SEI layer grows. SEI layer growth increases lithium inventory loss (LLI).

[0016] In lithium-ion battery cells with silicon-containing anodes, the SEI plays a particularly important role in capacity degradation due to the large volume changes during cycling. The expansion and contraction of the anode material often ruptures the SEI layer formed on top of it, exposing more of the anode material to direct contact with the electrolyte, which leads to further SEI generation and further LLI. This reduces the commercially useful charge cycle life of lithium-ion battery cells with silicon-containing anodes. Due to the surface area and shape of the silicon material at the anode-electrolyte interface, this problem of SEI rupture can be particularly severe for anodes comprising silicon with nanostructured surface morphology.

[0017] An object of the present disclosure is to provide a lithium ion battery cell including an anode, wherein the anode includes silicon, which has enhanced specific capacity and charge cycle stability.

[0018] Overview of the Disclosure

[0019] In view of the above discussion, a first aspect of the present disclosure is directed to a lithium-ion battery cell comprising:

[0020] - a silicon anode, the silicon anode comprising:

[0021] i. a current collector layer; and

[0022] ii. a silicon layer, which is located on the current collector layer,

[0023] wherein the silicon layer includes a plurality of columnar structures on the current collector;

[0024] -cathode;

[0025] - partitions; and

[0026] - an electrolyte comprising:

[0027] i. 9 wt.% to 29 wt.% of a lithium salt relative to the electrolyte;

[0028] ii. non-aqueous solvent; and

[0029] iii. diluent,

[0030] The electrolyte has a lithium salt-solvent-diluent molar ratio of 1:x:y, wherein x is in the range of 1.0 to 3.0, and y is in the range of 2.0 to 4.0.

[0031] Another aspect of the present disclosure relates to a lithium-ion battery cell produced by a process comprising the steps of:

[0032] (i) providing a lithium-ion battery cell according to the present invention;

[0033] (ii) charging the battery cell to a voltage of at least 4.0 V;

[0034] (iii) Discharge the voltage to 3.0V.

[0035] Another aspect of the present disclosure is a lithium-ion battery cell produced by a process comprising the steps of:

[0036] (i) providing a lithium-ion battery cell according to the present invention;

[0037] (ii) charging the battery cell at 0.01C for 10 hours;

[0038] (iii) charging the battery cell at 0.1C for (i) 9 hours or (ii) until it reaches 4.2V;

[0039] (iv) Discharge at 0.1C until reaching 2.5V;

[0040] (v) charging at 0.2C until reaching 4.2V;

[0041] (vi) discharging at 0.2C until reaching 2.5V; and

[0042] (vii) Charge at 0.2C for 90 minutes.

[0043] Another aspect of the present disclosure relates to a lithium-ion battery cell comprising:

[0044] - a silicon anode, the silicon anode comprising:

[0045] i. current collector layer;

[0046] ii. a silicon layer on the current collector layer; and

[0047] iii. Solid electrolyte interface layer,

[0048] The silicon layer includes:

[0049] i. A plurality of columnar structures on the current collector;

[0050] ii. a primary void having a width of 1 μm to 10 μm; and

[0051] iii. Optionally, a secondary void having a width of 10 nm to 150 nm;

[0052] -cathode;

[0053] - partitions; and

[0054] - an electrolyte comprising:

[0055] i. lithium salts;

[0056] ii. non-aqueous solvent; and

[0057] iii. diluent.

[0058] In another aspect, the present disclosure relates to a battery comprising a lithium-ion battery cell according to any of the preceding aspects. Another aspect of the present disclosure is the use of a lithium-ion battery cell according to any of the preceding aspects as an energy storage and / or release device.

[0059] Yet another aspect of the present disclosure relates to an electrolyte comprising:

[0060] - 9 to 29 wt.% of lithium bis(fluorosulfonyl)imide;

[0061] -1,2-dimethoxyethane; and

[0062] -1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether,

[0063] The electrolyte has a molar ratio of (lithium bis(fluorosulfonyl)imide):(1,2-dimethoxyethane):(1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether) of 1:x:y, wherein 1.3≤x≤3.0 and 2.0≤y≤4.0.

[0064] Cells and batteries according to the present disclosure provide unexpected and excellent cycle life and capacity properties.

[0065] A brief description of the attached figure

[0066] Figure 1 A conventional silicon anode material is depicted schematically and in block diagram form in a first unlithiated state (top), a fully lithiated state (middle), and a fully delithiated state (bottom).

[0067] Figure 2 Schematic depiction of a conventional silicon anode material during SEI formation, in a first unlithiated state (top), a fully lithiated state (middle), and a fully delithiated state (bottom).

[0068] Figure 3 A schematic depiction of a silicon anode material wherein the silicon layer comprises a plurality of pillar-like structures on a current collector. It depicts the silicon anode material in a first unlithiated state (top), a fully lithiated state (middle), and a fully delithiated state (bottom).

[0069] Figure 4A schematic depiction of a silicon anode material, wherein the silicon layer includes (i) a plurality of columnar structures on a current collector and (ii) a SEI. It depicts the silicon anode material in a first unlithiated state (top), a fully lithiated state (middle), and a fully delithiated state (bottom).

[0070] Figure 5 Schematically depicts a silicon anode material in a lithium battery cell according to the present invention. It depicts the silicon anode in a first unlithiated state (top), a fully lithiated state (middle) and a fully delithiated state (bottom).

[0071] Fig. 6A and Figure 6B Depicts a scanning electron microscope image obtained from an anode comprising a silicon layer ( Fig. 6A It is a top view. Figure 6B is a cross section), wherein the silicon layer includes a plurality of columnar structures.

[0072] Fig. 7A is the area capacity (mAh / cm 2 ) is a graph of the number of cycles experimentally obtained for materials according to the present disclosure (Example 3) and the comparative example (Example 3A).

[0073] Figure 7B is a graph of capacity retention (%) versus number of cycles experimentally obtained for materials according to the present disclosure (Example 3) and a comparative example (Example 3A).

[0074] Figure 7C is a graph of cumulative specific capacity (Ah / g) versus number of cycles experimentally obtained for materials according to the present disclosure (Example 3, straight solid line) and comparative examples (Example 3A, curved solid line).

[0075] Fig. 8A is a graph of capacity retention (%) versus cycle number experimentally obtained for materials according to the present disclosure (Example 6, top line) and the comparative example (Example 6A, lower line).

[0076] Figure 8B is a graph of Coulombic efficiency (%) versus number of cycles experimentally obtained for materials according to the present disclosure (Example 6, top line) and the comparative example (Example 6A, bottom line).

[0077] Fig.9A are SEM images of the anode surfaces of Example 3 (left) and Comparative Example 3A (right) after performing Method 6 at 0% state of charge.

[0078] Fig. 9Bare SEM images of the anode surfaces of Example 3 (left) and Comparative Example 3A (right) after performing Method 6 at a 50% state of charge.

[0079] Definitions and abbreviations

[0080] The subject matter disclosed in the present application will now be described more fully. However, the subject matter disclosed in the present application can be embodied in different forms and should not be construed as being limited to the embodiments set forth in the following and attached examples herein. More specifically, these embodiments are provided so that the present disclosure will be thorough and complete, and the scope of the embodiments will be fully conveyed to those skilled in the art.

[0081] All references listed herein, including but not limited to all patents, patent applications and publications thereof, and scientific journal articles, are hereby incorporated by reference in their entirety to the extent that they supplement, explain, provide context for, or teach the methods, techniques, and / or compositions employed herein.

[0082] While the following terms are believed to be well understood by those of ordinary skill in the art, the following definitions are set forth to facilitate explanation of the presently disclosed subject matter.

[0083] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the presently disclosed subject matter belongs.

[0084]

[0013] Following long-standing patent law convention, the terms "a," "an," and "the" mean "one or more" when used in this application, including the claims.

[0085] When used to describe two or more items or conditions, the term "and / or" refers to instances where all of the named items or conditions are present or applicable, or to instances where only one (or less than all) of the items or conditions are present or applicable.

[0086] Unless explicitly stated to refer to only alternatives or the alternatives are mutually exclusive, use of the term "or" in the claims is intended to mean "and / or," although the present disclosure supports a definition referring to only alternatives and "and / or."

[0087] As used herein, "another" may mean at least a second or more.

[0088] The term "comprising," which is synonymous with "including," "containing," or "characterized by," is inclusive or open-ended and does not exclude additional, unrecited elements or method steps.

[0089] “Comprising” is a technical term used in claim language, which means that the named elements are essential, but other elements may be added and still form a structure within the scope of the claim.

[0090] As used herein, the phrase "consisting of excludes any element, step, or ingredient not specified in the claim. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the preamble, it is limited only to the elements set forth in that clause; other elements are not excluded from the claim as a whole.

[0091] As used herein, the phrase "consisting essentially of limits the scope of a claim to the specified materials or steps and those that do not materially affect the basic and novel characteristics of the claimed subject matter. Unless otherwise indicated, all numbers expressing quantities of size, volume, percentage (%) and the like used in the specification and claims are to be understood as being modified in all instances by the word "about".

[0092] Accordingly, unless indicated to the contrary, the numerical parameters set forth in the specification and attached claims are approximations that may vary depending upon the desired properties sought to be obtained by the presently disclosed subject matter.

[0093] Additive: As used herein, the term "additive" refers to an electrolyte component present in an amount of 0.01 wt.% to 10 wt.%.

[0094] Amorphous silicon: The term "amorphous silicon" herein is understood to include protocrystalline silicon, which is a definition of amorphous silicon that includes a portion of nanocrystalline silicon. This portion can be up to about 30% of the silicon layer. For ease of reference, the term amorphous silicon will be used herein to indicate that the silicon layer includes amorphous silicon, wherein the nanocrystalline region of the silicon layer can contain up to about 30% nanocrystalline silicon.

[0095] Anode: The term "anode" is understood herein as an electrode through which charge flows into an electronic device. In the context of an electrochemical point of view, anions (i.e., negatively charged ions) move toward the anode, and / or cations (i.e., positively charged ions) move away from the anode to balance the electrons leaving the electrode to the electronic device. When discharging a lithium-ion battery or galvanic cell, the anode is the negative terminal from which electrons flow out. When charging or recharging a lithium-ion battery, the anode becomes the positive terminal into which electrons flow from the electronic device.

[0096] Capacity: The term "capacity" of a battery or battery cell is understood herein as the amount of charge that such a device can deliver. Capacity is expressed in units of mAh or Ah and indicates the maximum constant current that a battery or battery cell can produce in one hour. For example, a battery with a capacity of 1Ah can provide a current of 1A for 1 hour or 100mA for 10 hours.

[0097] Cathode: The term "electrode" is understood herein as the electrode through which charge flows out of the electronic device. In the context of an electrochemical point of view, anions (negatively charged ions) move away from the anode and / or cations (positively charged ions) move toward the anode to balance the electrons entering the electrode from the electronic device. When discharging a lithium-ion battery or galvanic cell, the cathode is the positive terminal into which the electrons flow. When charging or recharging a lithium-ion battery, the cathode becomes the negative terminal from which the electrons flow out to the electronic device.

[0098] Battery cell: The term "battery cell" is understood herein as an electrochemical device for generating a voltage or an electric current from a chemical reaction or conversely where an applied electric current causes a chemical reaction.

[0099] Coulombic efficiency (CE): The term "Coulombic efficiency" is understood herein as the efficiency with which charge is transferred in a cell or battery. Coulombic efficiency may be defined as the amount of charge that leaves a cell or battery during a discharge cycle divided by the amount of charge that entered the cell or battery during the previous charge cycle.

[0100] DME: herein means 1,2-dimethoxyethane.

[0101] DEC: herein stands for diethyl carbonate.

[0102] Doping: The term "doping" is understood herein as the introduction of trace elements into a material to change the original electrical properties of the material or to improve the crystal structure of the silicon material.

[0103] EC: herein stands for ethylene carbonate.

[0104] Electrolyte: refers herein to a substance containing free ions that behaves as an ionically conductive medium. In the context of this disclosure, an electrolyte includes ions in solution.

[0105] FEC: refers herein to fluoroethylene carbonate.

[0106] Fluoroalkyl: refers herein to an alkyl group in which at least one CH bond has been replaced by a CF bond.

[0107] Fluoroalkyl ether: In the context of this disclosure, the term refers to a fluoroalkyl ether having the general formula R 1 -OR 2A fluorinated ether, wherein R 1 and R 2 At least one of R is independently selected from fluoroalkyl. The fluoroalkyl chain may be linear, cyclic or branched. The fluoroalkyl ether may be partially or fully fluorinated. 1 and R 2 May be the same as or different from each other.

[0108] LiFSI: herein refers to lithium bis(fluorosulfonyl)imide.

[0109] Perfluoroalkyl group: refers herein to an alkyl group in which all CH bonds have been replaced by CF bonds.

[0110] Silicon anode: herein means a silicon anode is an anode wherein the majority of the mass is silicon, preferably at least 60 wt.%, more preferably at least 70 wt.%, and most preferably at least 80 wt.%.

[0111] Specific area capacity: In this article, it refers to the capacity per unit area of ​​the electrode or active material. The unit of specific area capacity is mAh / cm 2 .

[0112] Specific capacity: In this context, it refers to the capacity per unit mass. In this patent, mass specifically refers to the mass of silicon active material in the anode. Specific capacity can be expressed in mAh / g.

[0113] Solid Electrolyte Interface (SEI): refers herein to a passivation layer comprising decomposed species resulting from the electrochemical decomposition of the electrolyte at the electrode / electrolyte phase boundary of the anode. This is typically formed during the first few cycles of a lithium-ion battery or cell.

[0114] TTE: herein means 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0115] Detailed Description of the Invention

[0116] Lithium-ion battery cells

[0117] The present disclosure relates to a lithium-ion battery cell, comprising:

[0118] - a silicon anode, the silicon anode comprising:

[0119] i. a current collector layer; and

[0120] ii. Silicon layer,

[0121] wherein the silicon layer includes a plurality of columnar structures on the current collector;

[0122] -cathode;

[0123] - partitions; and

[0124] - an electrolyte comprising:

[0125] i. 9 wt.% to 29 wt.% of a lithium salt relative to the electrolyte;

[0126] ii. non-aqueous solvent; and

[0127] iii. diluent,

[0128] The electrolyte has a lithium salt-solvent-diluent molar ratio of 1:x:y, wherein 1.0≤x≤3.0 and 2.0≤y≤4.0.

[0129] The lithium ion battery cells according to this aspect of the disclosure surprisingly exhibit excellent cycle life and current density.

[0130] anode

[0131] A lithium-ion battery cell according to the present disclosure includes a silicon anode. The silicon anode includes a silicon layer and a current collector layer.

[0132] Current Collector

[0133] Preferably, the current collector materials according to the present disclosure each have a thickness of 1 μm to 100 μm, preferably 5 μm or 10 μm to 50 μm, more preferably 10 μm to 15 μm, or about 10 μm or 12 μm.

[0134] Advantageously, the current collector material according to the present disclosure may include copper, tin, chromium, nickel, titanium, stainless steel or silver, or alloys thereof, more preferably copper or nickel, or alloys thereof, most preferably copper.

[0135] The current collector material includes a sheet material produced by cold rolling or electroplating, and may also include an alloy of copper or titanium with elements such as magnesium, zinc, tin, phosphorus and / or silver. It may be smooth, rough or textured, with a tensile strength preferably of 150MPa to 600MPa, and may include a passivation layer deposited on the copper foil to protect the copper foil from oxidation in the air. The sheet material produced by cold rolling or electroplating may have certain defects, such as rolling lines, potential strains, impurities and native oxides, which may affect the quality of the active material layer. Therefore, the current collector material may be surface treated. For example, by attaching the nodules of the current collector material or other metals to the surface of the current collector material, such as by electroplating, the roughness of the foil may be increased to varying degrees. Other surface treatment techniques known in the art include annealing, knurling, etching, liquefaction, physical polishing and electropolishing, and are used to improve the morphology of the current collector material before depositing the active material.

[0136] Preferably, the current collector material according to the present disclosure comprises a metal, a metal alloy and / or a metal salt and / or an oxide. The metal, metal alloy and / or metal salt and / or oxide according to the present disclosure is advantageously selected from aluminum, copper, nickel, tin, tin, indium and zinc, preferably nickel, ZnO or SnO2, most preferably ZnO; preferably, wherein the current collector comprises a copper or nickel core layer, more preferably a core layer doped with an oxide or fluoride of zinc, aluminum, tin or indium. Preferably, the metal, metal alloy and / or metal salt and / or oxide or core layer is in a layer having a thickness of 0.1 nm to 5 nm, more preferably 1 nm to 2 nm. Preferably, the current collector comprising copper or nickel according to the present disclosure comprises nickel, ZnO or SnO2.

[0137] Optional interstitial adhesion layer

[0138] In the current applicant's pending international patent application WO2021029769, it is disclosed that an adhesion layer comprising a metal, metal alloy and / or metal salt and / or oxide attached to a current collector material can advantageously increase the adhesion of a silicon material to the current collector material of a composite electrode. This interstitial adhesion layer is not required. According to the present disclosure, the current collector material comprising an adhesion layer of a metal, metal alloy and / or metal salt and / or oxide preferably includes an adhesion layer. The adhesion layer increases the adhesion between the silicon material and the current collector material because different silicon composites are formed at the interface between the current collector material and silicon. This adhesion layer preferably includes nickel, zinc or tin, such as ZnO or SnO2. The adhesion layer can be formed by coating or depositing a metal, metal alloy and / or metal salt and / or oxide on the current collector material. Preferably, the adhesion layer is located in a layer having a thickness of 0.1nm to 5nm, more preferably 1nm to 2nm.

[0139] Silicon layer

[0140] The silicon layer of the silicon anode includes a plurality of columnar structures on the current collector. The silicon layer exists on the current collector layer.

[0141] The silicon layer according to the present disclosure is attached to the current collector layer as a layer comprising a plurality of adjacent pillars having a diameter of 0.5 μm to 100 μm, either directly or by attachment to an interstitial adhesion layer.

[0142] Preferably, the columns have a diameter of 1 to 75 μm, more preferably 2 to 50 μm, even more preferably 3 to 25 μm, still more preferably 4 to 20 μm, even more preferably 5 to 15 μm, still more preferably 6 to 12 μm, most preferably 8 to 10 μm.

[0143] Preferably, the pillars have an average diameter of 1 μm to 75 μm, more preferably 2 μm to 50 μm, even more preferably 3 μm to 25 μm, still more preferably 4 μm to 20 μm, even more preferably 5 μm to 15 μm, still more preferably 6 μm to 12 μm, most preferably 8 μm to 10 μm.

[0144] Preferably, the columns extend primarily in a vertical direction from the surface of the current collector layer. In this context, adjacent columns may advantageously be separated by column boundaries extending substantially in a vertical direction. This can be determined by cross-sectional electron microscopy.

[0145] Preferably, according to the present disclosure, at least one silicon layer has a thickness of 0.1 μm to 1,000 μm, preferably 0.5 μm to 500 μm, more preferably 1 μm to 100 μm or 200 μm, even more preferably 1 μm to 30 μm or 50 μm, still more preferably 3 μm to 20 μm, still more preferably 5 μm to 15 μm, and most preferably 6 μm to 10 μm. Alternatively, according to the present disclosure, at least one silicon layer has a mass loading of preferably 0.1 mg / cm 2 Up to 4.0mg / cm 2 , more preferably 0.5 mg / cm 2 or 0.8mg / cm 2 Up to 2.0mg / cm 2 Up to 2.5 mg / cm 2 , or 2.5mg / cm 2 Up to 3.5mg / cm 2 or 4.0mg / cm 2 , most preferably 1.0 mg / cm 2 Up to 2.0mg / cm 2 The mass loading refers to the mass loading of a silicon layer present on one side of the current collector layer.

[0146] Advantageously, at least one silicon layer according to the present disclosure has a porosity of 0% to 50%, more preferably 1%, 2%, 5% or 10% to 50%.

[0147] Preferably, the silicon layer according to the present disclosure has a porosity of 0% to 80%, preferably 5%-60%, even more preferably 10%-40%, as determined by the BJH method of ISO 15901-2:2006.

[0148] Preferably, the average pore size of the silicon layer is in the range of 0.5 nm to 40 nm, preferably in the range of 1 nm to 20 nm.

[0149] The porosity and (average) pore size according to the present disclosure are preferably determined using nitrogen according to the method specified by the ISO (International Organization for Standardization) standard: ISO 15901-2:2006 "Pore size distribution and porosity of solid materials by mercury porosimetry and gas adsorption—Part 2: Analysis of mesopores and macropores by gas adsorption". In short, the N2 adsorption isotherm is measured at about -196°C (liquid nitrogen temperature). The pore size and pore volume can be determined according to the calculation method of Barrett-Joyner-Halenda (Barrett, EP; Joyner, LG; Halenda, PP (1951), "The Determination of Pore Volume and Area Distributions in Porous Substances. I. Computations from Nitrogen Isotherms", Journal of the American Chemical Society, 73(1):373-380). The specific surface area can be determined from the same isotherm according to the Brunauer-Emmett-Teller calculation method (Brunauer, S.; Emmett, PH; Teller, E. (1938), "Adsorption of Gases in Multimolecular Layers", Journal of the American Chemical Society, 60 (2): 309-319). Both calculation methods are well known in the art. A simple experimental test method for determining the isotherm can be described as follows: The test sample is dried at high temperature and in an inert atmosphere. The sample is then dried and placed in a measuring instrument. Next, the sample is placed under vacuum and cooled using liquid nitrogen. During the recording of the isotherm, the sample is kept at liquid nitrogen temperature.

[0150] The silicon layer according to the present disclosure preferably has an amorphous structure in which nanocrystalline regions are present. More preferably, the silicon layer or pillar comprises up to 30% nanocrystalline silicon. According to one embodiment, the silicon layer advantageously comprises an n-type or p-type dopant to obtain a silicon layer having n-type conductivity or p-type conductivity, respectively.

[0151] Advantageously, the silicon column may also include a silicon alloy, wherein the silicon alloy is preferably selected from the group including Si-C and / or Si-N. Preferably, the composite material according to the present disclosure includes: carbon or an alloy containing carbon or silicon. The silicon alloy may be an additive or substitute for amorphous silicon. Therefore, according to aspects of the present disclosure, the material of the column includes at least one material selected from amorphous silicon and amorphous silicon alloys.

[0152] According to another aspect, the material of the column comprises amorphous silicon and a nanocrystalline silicon alloy. In some embodiments, the silicon alloy may be present in the electrode layer as a nanocrystalline phase. In addition, the anode layer may comprise a mixture of an amorphous material and a nanocrystalline phase. For example, a mixture of amorphous silicon and nanocrystalline silicon, or a mixture of amorphous silicon and a nanocrystalline silicon alloy, or a mixture of silicon and a silicon-based alloy that is primarily in an amorphous state, comprises a portion (up to about 30%) of the mixture that is in a nanocrystalline state. According to the present disclosure, the amorphous silicon column preferably extends in a vertical direction from the anode surface (i.e., the interface between the anode layer and the electrolyte layer), wherein a plurality of silicon columns are arranged adjacent to each other while being separated by an interface extending perpendicular to the anode surface.

[0153] The silicon layer according to the present disclosure may advantageously include silicon oxide. The silicon layer according to the present disclosure may be positioned on the current collector layer in various configurations. The silicon may be on a nanowire template, which is attached to a substrate, such as a current collector layer or an adhesion layer. The term "nanowire" herein is understood to be a branched or non-branched linear structure having at least one dimension and a length of up to about 1 μm. Nanowires are conductive materials, including, for example, carbon, metals or metal silicides, such as nickel silicide, copper silicide, silver silicide, chromium silicide, cobalt silicide, aluminum silicide, zinc silicide, titanium silicide or iron silicide, preferably including at least one nickel silicide phase containing Ni2Si, NiSi or NiSi2. The nanowires may be the same material as the current collector, such as nickel, copper or titanium. Alternatively, the nanowires may be materials and layers separate from the current collector material (e.g., a copper current collector coated with a nickel layer). One or more layers of active material (such as silicon) may be deposited on the nanowires by, for example, PVD, CVD or PECVD. The silicon layer may include carbon, copper, sulfide, metal oxide, fluorine-containing compound, polymer or lithium phosphorus oxynitride. The silicon layer may be coated with a layer comprising carbon, copper, sulfide, metal oxide, fluorine-containing compound, polymer or lithium phosphorus oxynitride, preferably a carbon layer with a thickness of 1 nm to 5 μm, preferably a thickness of 10 nm to 1 μm.

[0154] Optional electrode tabs

[0155] In a preferred embodiment, the lithium-ion battery cell according to the present disclosure further comprises an electrode tab. More preferably, the lithium-ion battery cell according to the present disclosure further comprises an electrode tab comprising nickel or copper or an alloy comprising nickel, copper, tin, silicon, copper and nickel, copper and tin, or copper and silicon. Most preferably, the tab material comprises nickel.

[0156] The tab is preferably a sheet material comprising metal having a thickness of 1 μm to 1 mm, more preferably 10 μm to 500 μm, 20 μm to 200 μm, 50 μm to 150 μm or about 100 μm.

[0157] cathode

[0158] A battery cell according to the present disclosure includes a cathode. Cathodes suitable for use in the present disclosure are known to those skilled in the art and are commercially available.

[0159] Preferably, the cathode or the positive electrode or the material they consist essentially of is selected from:

[0160] Carbon / sulfur composites or air electrodes, in particular carbon-based electrodes, comprising graphitic carbon and optionally a metal catalyst such as Ir, Ru, Pt, Ag or Ag / Pd; carbon monofluoride; CuO (copper oxide); Cr2O5; Cr3O8; iron disulfide; Li2M 2 SiO4(M 2 =Mn, Fe or Co), Li2M 2 SO4(M 2 =Mn, Fe or Co), LiM2SO4 m F (M2 = Fe, Mn or Co), Li 2-x (Fe 1-y Mn y )P2O7(0≤x≤1;0≤y≤1), Li3V 2-x M1 x (PO4)3(M1=Cr, Co, Fe, Mg, Y, Ti, Nb or Ce; 0≤x≤1); Li 4- x M x Ti5O 12 (M=Mg, Al, Ba, Sr or Ta; 0≤x≤1); LiCoO2; LiFePO4(LFP); LiMC1 x MC 2 1-x O2 (MC1 and MC2 are Fe, Mn, Ni, Co, Cr, Ti, Mg or Al; 0≤x≤1); LiMC1 x MC2 1-xPO4(MC1 or MC2=Fe, Mn, Ni, Co, Cr or Ti; 0≤x≤1); LiMC1 x MC2 y MC3 1-x-y O2 (MC1, MC2 and MC3 are Fe, Mn, Ni, Co, Cr, Ti, Mg or Al respectively; 0≤x≤1; 0≤y≤1, 0≤x+y≤1); LiMn2O4 (LMO); LiMn 2-y X y O4(X=Cr, Al or Fe, 0≤y≤1); LiNi 0.5 Mn 1.5 O4 spinel; LiNi 0.5-y X y Mn 1.5 O4 (X=Fe, Cr, Zn, Al, Mg, Ga, V or Cu; 0≤y<0.5); LiNi 0.8 Co 0.15 Al 0.05 O2(NCA);LiNi x Mn y Co Z O2 (NMC, x+y+z=1), Li-rich Li 1+w Ni x Mn y Co Z O2(x+y+z+w=1,0≤w≤0.25); LiV3O8; LiVPO4F; MnO2; thionyl chloride; V2O5; V6O1; xLi2MnO3(1-x)LiM 1 y M 2 M 3 1-y- z O2, where M 1 、M 2 and M 3 Respectively Mn, Ni, Co, Cr, Fe or a mixture thereof; and wherein x=0.3-0.5; y≤0.5; z≤0.5.

[0161] In a preferred embodiment, the cathode is a lithium conversion compound such as Li2O2, Li2O, Li2S or LiF. More preferably, the cathode comprises LiNi X Mn Y Co Z O2, where x ≥ 0.6 (NMC) or LiNi x Mg y Ti 1-x-y O2, where 0.9≤x<1(NMT; e.g., LiNi 0.96 Mg0.02 Ti 0.02 O2).

[0162] In a particularly preferred embodiment, the cathode is selected from one or more high voltage cathodes, which means a cathode that can be operated at 4.3V to 4.6V.

[0163] Partition

[0164] A battery cell according to the present disclosure includes a separator. The separator is present to prevent a short circuit from forming between the cathode and the anode while still allowing ions to flow between the two electrodes.

[0165] The separator may be appropriately selected from: (i) glass fibers; (ii) porous polymer films with or without ceramic coatings, such as polyethylene or polypropylene-based materials, or (iii) composite materials (e.g., porous films of inorganic particles and binders). An exemplary polymer separator is K1640 polyethylene (PE) film. Another exemplary polymer separator is 2500 polypropylene film. Another exemplary polymer separator is 3501 surfactant coated polypropylene film.

[0166] Another group of exemplary porous polymer membranes with ceramic coatings are PE and PP separators available from Gelon. An example of such a separator is the Gelon 16 μm thick PE battery separator, which comprises a 12 μm thick polyethylene polymer film coated on both sides with a 2 μm thick ceramic alumina layer to provide a separator with a porosity of 38%.

[0167] The separator may optionally be impregnated with electrolyte.

[0168] Electrolytes

[0169] A battery cell according to the present disclosure includes an electrolyte. The electrolyte includes:

[0170] i. 9 wt.% to 29 wt.% of a lithium salt relative to the electrolyte;

[0171] ii. non-aqueous solvent;

[0172] iii. diluent;

[0173] The electrolyte has a lithium salt-solvent-diluent molar ratio of 1:x:y, wherein 1.0≤x≤3.0 and 2.0≤y≤4.0.

[0174] Lithium salts

[0175] The electrolyte includes 9 wt. % to 29 wt. % of a lithium salt relative to the electrolyte.

[0176] Lithium salts or combinations of lithium salts are involved in the charging and discharging process of the battery cell.

[0177] Preferably, the lithium salt includes: LiAsF6, Li2SO4, LiBF4, LiBr, LiCF3SO3, LiCl, LiClO4, LiI, LiNO2, LiNO3, LiSCN, 2-trifluoromethyl-4,5-dicyanoimidazole lithium (CAS: 761441-54-7), (fluorosulfonyl) (trifluoromethylsulfonyl) imide lithium (LiFTFSI), bis (fluorosulfonyl) imide lithium (LiFSI); bis (oxalate) borate lithium (LiBOB), bis (pentafluoroethanesulfonyl) imide lithium (LiBETI), bis (trifluoromethanesulfonyl) imide lithium (LiTFSI), difluoro (oxalate) borate lithium (LiDFOB CAS: 409071-16-5), trifluoromethanesulfonate lithium (LiTf), LiPF6 or any combination thereof.

[0178] More preferably, the electrolyte comprises 9 wt.% to 29 wt.% of a lithium salt, relative to the electrolyte, selected from the group consisting of LiAsF6, Li2SO4, LiBF4, LiBr, LiCF3SO3, LiCl, LiClO4, LiI, LiNO2, LiNO3, LiSCN, 2-trifluoromethyl-4,5-dicyanoimidazole lithium (CAS: 761441-54-7), (fluorosulfonyl)(trifluoromethylsulfonyl)imide lithium (LiFTFSI), bis(fluorosulfonyl)imide lithium (LiFSI); bis(oxalate)borate lithium (LiBOB), bis(pentafluoroethanesulfonyl)imide lithium (LiBETI), bis(trifluoromethanesulfonyl)imide lithium (LiTFSI), difluoro(oxalate)borate lithium (LiDFOB CAS: 409071-16-5), trifluoromethanesulfonate lithium (LiTf), LiPF6 or any combination thereof.

[0179] Most preferably, the lithium salt consists essentially of lithium bis(fluorosulfonyl)imide.

[0180] Non-aqueous solvents

[0181] The electrolyte comprises a non-aqueous solvent. Advantageously, the non-aqueous solvent is selected such that the lithium salt has a solubility in the selected solvent of at least 3 M (mole / dm 3 ).

[0182] Preferably, the non-aqueous solvent is selected such that the lithium salt has a solubility in the selected solvent of at least 4 M at 25°C and 1 atm, more preferably at least 5 M at 25°C and 1 atm.

[0183] Without being limited by theory, it is believed that the solvent molecules in the electrolyte according to the present disclosure are statistically most likely to be tightly associated with the lithium ion salt to form aggregates. It is further believed that these solvent-lithium salt aggregates are suspended in the continuous phase of the diluent.

[0184] Preferably, the non-aqueous solvent is selected from a non-aqueous solvent comprising at least one of the following components: (i) esters, (ii) sulfur-containing solvents, (iii) phosphorus-containing solvents, (iv) ethers, (v) nitriles, or (vi) any combination thereof.

[0185] Ester solvent

[0186] Preferably, the ester is selected from: diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dimethyl carbonate (DMC), methyl ethyl carbonate (EMC), ethylene carbonate (EC), methyl 2,2,2,-trifluoroethyl carbonate (MFEC), propylene carbonate (PC), trifluoroethylene carbonate (TFEC), trifluoropropylene carbonate (TFPC), 2,2,2,-trifluoroethyl trifluoroacetate, ethyl 2,2,2-trifluoroacetate, alkyl carboxylate (such as ethyl acetate), ethyl propionate, ethyl trifluoroacetate, methyl butyrate or any combination thereof.

[0187] More preferably, the ester is selected from: 2,2,2,-trifluoroethyl trifluoroacetate, 2,2,2-ethyl trifluoroacetate, ethyl acetate, ethyl acetate, ethyl propionate, ethyl trifluoroacetate, methyl butyrate and / or any combination thereof.

[0188] Sulfur-containing solvents

[0189] Preferably, the sulfur-containing solvent is selected from sulfone solvents, sulfoxide solvents or any combination thereof. More preferably, the sulfur-containing solvent is selected from dimethyl sulfone, dimethyl sulfone, ethyl methyl sulfone (EMS), ethyl vinyl sulfone (EVS), tetramethylene sulfone (TMS, sulfolane), dimethyl sulfoxide, ethyl methyl sulfoxide, ethyl methyl sulfone (EMS), ethyl vinyl sulfone (EVS), tetramethylene sulfone (TMS, sulfolane), dimethyl sulfoxide, ethyl methyl sulfoxide or any combination thereof.

[0190] Phosphorus-containing solvents

[0191] Preferably, the phosphorus-containing solvent is selected from organophosphorus compounds (such as organophosphates, phosphites, phosphonates, phosphoramides), phosphazenes (organic or inorganic) or any combination thereof.These phosphorus-containing solvents are typically flame retardants.

[0192] More preferably, the phosphorus-containing solvent is selected from: bis(2,2,2-trifluoroethyl)methyl phosphate, tributyl phosphate, triethyl phosphate (TEPa), trimethyl phosphate (TMPa), triphenyl phosphate, tris(2,2,2-trifluoroethyl) phosphate, trimethyl phosphite, triphenyl phosphite, tris(2,2,2-trifluoroethyl) phosphite, dimethyl methyl phosphonate; diethyl ethyl phosphonate, diethyl phenyl phosphonate, bis(2,2,2-trifluoroethyl) methyl phosphonate, hexamethylphosphoramide, hexamethoxyphosphazene (CAS: 957-13-1), hexamethoxycyclotriphosphazene (CAS: 6607-30-3), hexafluorophosphazene (CAS: 15599-91-4) or any combination thereof.

[0193] Ether solvent

[0194] Preferably, the ether solvent is selected from: 1,2-dimethoxyethane (DME), diethylene glycol dimethyl ether (DEGDME), triethylene glycol dimethyl ether (triglyme), tetraethylene glycol dimethyl ether (tetraglyme), 1,3-dioxolane (DOL), allyl ether or any combination thereof.

[0195] Nitrile solvents

[0196] Preferably, the nitrile solvent is selected from: acetonitrile, propionitrile, succinonitrile, adiponitrile (CAS: 111-69-3) or any combination thereof.

[0197] The electrolyte preferably includes a non-aqueous solvent selected from the following items: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), difluoroethylene carbonate (DFEC), trifluoroethylene carbonate (TFEC), trifluoropropylene carbonate (TFPC), methyl 2,2,2,-trifluoroethyl carbonate (MFEC), ethyl acetate, ethyl propionate, methyl butyrate; ethyl trifluoroacetate, ethyl 2,2,2-trifluoroethyl acetate, 2,2,2-trifluoroethyl trifluoroacetate, dimethyl sulfone (DMS), ethyl methyl sulfone (EMS), ethyl vinyl sulfone (EVS), tetramethylene sulfone (TMS), dimethyl sulfoxide, ethyl methyl sulfoxide, trimethyl phosphate (TMPa), triethyl phosphate (TEPa), trisphosphate ester, triphenyl phosphate, tris(2,2,2-trifluoroethyl) phosphate, bis(2,2,2-trifluoroethyl) methyl phosphate, trimethyl phosphite, triphenyl phosphite, tris(2,2,2-trifluoroethyl) phosphite, dimethyl methyl phosphonate, diethyl ethyl phosphonate, diethyl phenyl phosphonate, bis(2,2,2-trifluoroethyl) methyl phosphonate, hexamethylphosphoramide, hexamethoxyphosphazene, hexamethoxycyclotriphosphazene, hexafluorophosphazene, 1,2-dimethoxyethane (DME), diethylene glycol dimethyl ether (diglyme, DEGDME), triethylene glycol dimethyl ether (triglyme), tetraethylene glycol dimethyl ether (tetraglyme), 1,3-dioxolane (DOL), allyl ether, acetonitrile, propionitrile, succinonitrile, adiponitrile (CAS: 111-69-3) or any combination thereof.

[0198] Even more preferably, the non-aqueous solvent is selected from the group consisting of: ethyl acetate, ethyl propionate, methyl butyrate, ethyl trifluoroacetate, ethyl 2,2,2-trifluoroacetate, 2,2,2-trifluoroethyl trifluoroacetate; dimethyl sulfone (DMS), ethyl methyl sulfone (EMS), ethyl vinyl sulfone (EVS), tetramethylene sulfone (TMS), dimethyl sulfoxide, ethyl methyl sulfoxide, trimethyl phosphate (TMPa), triethyl phosphate (TEPa), tributyl phosphate, triphenyl phosphate, tris(2,2,2-trifluoroethyl) phosphate, bis(2,2,2-trifluoroethyl) methyl phosphate, trimethyl phosphite, triphenyl phosphite, tris(2 ,2,2-trifluoroethyl)phosphite, dimethyl methyl phosphonate, diethyl ethyl phosphonate, diethyl phenyl phosphonate, bis(2,2,2-trifluoroethyl)methyl phosphonate, hexamethylphosphoramide, hexamethoxyphosphazene (cyclo-tris(dimethoxyphosphazene), hexamethoxycyclotriphosphazene), hexafluorophosphazene (hexafluorocyclotriphosphazene), 1,2-dimethoxyethane (DME), diethylene glycol dimethyl ether (DEGDME, or diethylene glycol dimethyl ether), triethylene glycol dimethyl ether (triglyme), tetraethylene glycol dimethyl ether (tetraglyme), 1,3-dioxolane (DOL), allyl ether, acetonitrile, propionitrile, or any combination thereof.

[0199] Most preferably, the solvent is 1,2-dimethoxyethane (DME).

[0200] Dilution

[0201] The electrolyte includes a diluent. The diluent is advantageously selected so that the solubility of the lithium salt in the selected solvent is less than 0.3 M (mol / dm 3 ).

[0202] Preferably, the diluent is selected such that the solubility of the lithium salt in the selected diluent is less than 0.2M, more preferably less than 0.1M, even more preferably less than 0.05M, most preferably less than 0.01M at 25°C and 1 atm.

[0203] Preferably, the diluent is selected from diluents comprising one or more of the following: fluoroalkyl ethers; fluorinated orthoformates, fluorinated carbonates, fluorinated borates or combinations thereof.

[0204] More preferably, the diluent is selected from: fluoroalkyl ethers, fluorinated orthoformates, fluorinated carbonates, fluorinated borates or combinations thereof.

[0205] Even more preferably, the diluent is selected from the group consisting of: 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether (TTE), 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (TFTFE), 1,2,2,2-tetrafluoroethyl trifluoromethyl ether, 1H,1H,5H-octafluoropentyl 1,1,2,2-tetrafluoroethyl ether (OTE), bis(2,2,2-trifluoroethyl) carbonate, bis(2,2,2-trifluoroethyl) ether (BTFE), bis(2,2,2-trifluoroethyl) methyl orthoformate (BTF ... EMO), ethoxy nonafluorobutane (EOFB); heptafluoroisopropyl methyl ether; methoxy nonafluorobutane (MOFB), tris(2,2,2-trifluoroethyl)borate, tris(2,2,2-trifluoroethyl)orthoformate (TFEO), tris(2,2,3,3,3-pentafluoropropyl)orthoformate (TPFPO), tris(2,2,3,3-tetrafluoropropyl)orthoformate (TTPO), tris(2,2-difluoroethyl)orthoformate (TDFEO), tris(hexafluoroisopropyl)orthoformate (THFiPO), or any combination thereof.

[0206] Still more preferably, the diluent is selected from: 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether (TTE), 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (TFTFE), 1H,1H,5H-octafluoropentyl 1,1,2,2-tetrafluoroethyl ether (OTE), bis(2,2,2-trifluoroethyl) ether (BTFE), bis(2,2,2-trifluoroethyl) methyl orthoformate (BTFEMO), Ethoxy nonafluorobutane (EOFB); methoxy nonafluorobutane (MOFB), tris(2,2,2-trifluoroethyl)orthoformate (TFEO), tris(2,2,3,3,3-pentafluoropropyl)orthoformate (TPFPO), tris(2,2,3,3-tetrafluoropropyl)orthoformate (TTPO), tris(2,2-difluoroethyl)orthoformate (TDFEO), tris(hexafluoroisopropyl)orthoformate (THFiPO), or any combination thereof.

[0207] Most preferably, the diluent is 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether (TTE).

[0208] Electrolyte composition ratio

[0209] The electrolyte according to the present disclosure has a lithium salt-solvent-diluent molar ratio of 1:x:y, wherein 1.0≤x≤3.0 and 2.0≤y≤4.0.

[0210] Preferably, the electrolyte has a lithium salt-solvent-diluent molar ratio of 1:x:y, wherein 1.1≤x≤2.5 and 2.2≤y≤3.8, more preferably 1.2≤x≤2.0 and 2.4≤y≤3.6, even more preferably 1.2≤x≤1.8 and 2.6≤y≤3.4, and most preferably x=1.2 and y=3.0.

[0211] More preferably, the electrolyte is an electrolyte in which the lithium salt is lithium bis(fluorosulfonyl)imide, and the electrolyte has a lithium salt-solvent-diluent molar ratio of 1:x:y, wherein 1.1≤x≤21.5 and 2.2≤y≤3.8, more preferably 1.2≤x≤2.01.4 and 2.4≤y≤3.6, even more preferably 1.2≤x≤1.84 and 2.6≤y≤3.4, and most preferably x=1.2 and y=3.0.

[0212] Even more preferably, the electrolyte is an electrolyte wherein the lithium salt is lithium bis(fluorosulfonyl)imide and the non-aqueous solvent is 1,2-dimethoxyethane, wherein the electrolyte has a lithium salt-solvent-diluent molar ratio of 1:x:y, wherein 1.1≤x≤21.5 and 2.2≤y≤3.8, more preferably 1.2≤x≤2.01.4 and 2.4≤y≤3.6, even more preferably 1.2≤x≤1.84 and 2.6≤y≤3.4 and most preferably x=1.2 and y=3.0.

[0213] Still more preferably, the electrolyte is one in which the diluent is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, wherein the electrolyte has a lithium salt-solvent-diluent molar ratio of 1:x:y, wherein 1.1≤x≤21.5 and 2.2≤y≤3.8, more preferably 1.2≤x≤2.01.4 and 2.4≤y≤3.6, even more preferably 1.2≤x≤1.84 and 2.6≤y≤3.4, and most preferably x=1.2 and y=3.0.

[0214] Most preferably, the electrolyte is an electrolyte wherein the lithium salt is lithium bis(fluorosulfonyl)imide; the non-aqueous solvent is 1,2-dimethoxyethane; and the diluent is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, wherein the electrolyte has a lithium salt-solvent-diluent molar ratio of 1:x:y, wherein 1.1≤x≤21.5 and 2.2≤y≤3.8, more preferably 1.2≤x≤2.01.4 and 2.4≤y≤3.6, even more preferably 1.2≤x≤1.84 and 2.6≤y≤3.4 and most preferably x=1.2 and y=3.0.

[0215] additive

[0216] Preferably, the electrolyte according to the present disclosure further comprises an additive. The additive has a composition different from: (i) a lithium salt; (ii) a solvent; and (iii) a diluent. Optionally, the additive is a flame retardant.

[0217] Preferably, the additives include: 4-fluoro-1,3-dioxolane-2-one (FEC, CAS: 114435-02-8), 1,3-dioxol-2-one (VC, vinylene carbonate, CAS: 872-36-6), 1,4-dicyanobutane (adiponitrile, CAS: 111-69-3), lithium difluorophosphate (LiDFP), 4,5-dimethylene-1,3-dioxolane-2-one, 1,3,2-dioxathiolane-2-oxide (CAS: 3741-38-6) 1,3,2-dioxathiolane-2,2-dioxide (CAS: 1072-36-6). -53-3), 1,3,2-dioxathiacyclohexane-2,2-dioxide (DTD, CAS: 1072-53-3), 3-methyl-1,4,2-dioxazol-5-one (CAS: 854849-14-2), tris(2,2,2-trifluoroethyl)phosphite (TTFEPi, CAS: 370-69-4), 1,3,2-dioxathiacyclohexane-2-oxide (CAS: 4176-55-0), 1-methylsulfonylethylene (CAS: 3680-02-2), 1-vinylsulfonylethylene (CAS: 77-77--0) or any combination thereof.

[0218] Method for producing electrolyte

[0219] On the other hand, the present disclosure relates to a method for preparing an electrolyte according to the above aspects, comprising the following steps: dissolving 9 wt.% to 29 wt.% lithium bis(fluorosulfonyl)imide relative to the electrolyte in a non-aqueous solvent 1,2-dimethoxyethane; adding a 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether diluent to the solution containing the lithium salt; mixing the diluent / solution mixture until a uniform suspension is obtained.

[0220] Without being bound by theory, it is believed that the resulting electrolyte possesses favorable electrolyte properties.

[0221] Lithium-ion battery cell manufacturing

[0222] Another aspect of the present disclosure relates to a method of manufacturing a lithium-ion battery cell according to any of the preceding aspects or specific embodiments, comprising the steps of:

[0223] - Providing a silicon anode, the silicon anode comprising:

[0224] (i) a silicon layer; and

[0225] (ii) a current collector layer,

[0226] The silicon layer includes a plurality of columnar structures on the current collector;

[0227] - placing the separator onto the silicon anode;

[0228] - placing the cathode onto the separator to form a stack;

[0229] - Connecting the cathode and anode to the electrode tabs;

[0230] - inserting the stack of anode, separator and cathode into the cell housing;

[0231] - Adding electrolytes, the electrolytes comprising:

[0232] (i) 9 wt.% to 29 wt.% of a lithium salt relative to the electrolyte;

[0233] (ii) non-aqueous solvent;

[0234] (iii) diluent;

[0235] The electrolyte has a lithium salt-solvent-diluent molar ratio of 1:x:y, wherein 1.0≤x≤3.0 and 2.0≤y≤4.

[0236] - Sealing the cell housing to prevent the electrolyte from being able to leave the cell housing.

[0237] In the context of this aspect of the disclosure: (i) the silicon anode; (ii) the separator; (iii) the cathode; (iv) the electrolyte may be as described in any preceding aspect or in the specific embodiments above.

[0238] Preferably, the battery cell housing is a pouch. More preferably, the battery cell housing is a laminated aluminum pouch.

[0239] Preferably, the step of sealing the battery cell housing is performed in a dry atmosphere. More preferably, the step of sealing the battery cell housing is performed under an inert atmosphere. As non-limiting examples, such an inert atmosphere may be nitrogen or argon.

[0240] Another aspect of the present disclosure relates to a method of manufacturing a lithium-ion battery cell according to any of the preceding aspects or specific embodiments, comprising the steps of:

[0241] - Providing a silicon anode, the silicon anode comprising:

[0242] (i) a first silicon layer;

[0243] (ii) a second silicon layer; and

[0244] (iii) a current collector layer,

[0245] The silicon layer includes a plurality of columnar structures on the current collector;

[0246] - placing a first separator onto the first silicon layer of the silicon anode;

[0247] - placing a second separator onto the second silicon layer of the silicon anode;

[0248] - placing a first cathode on the first separator;

[0249] - placing a second cathode onto the second separator to form a stack;

[0250] - Connecting the cathode and anode to the electrode tabs;

[0251] - inserting the stack of anode, separator and cathode into the cell housing;

[0252] - Adding electrolytes, the electrolytes comprising:

[0253] (i) 9 wt.% to 29 wt.% of a lithium salt relative to the electrolyte;

[0254] (ii) non-aqueous solvent;

[0255] (iii) diluent;

[0256] The electrolyte has a lithium salt-solvent-diluent molar ratio of 1:x:y, wherein 1.0≤x≤3.0 and 2.0≤y≤4.

[0257] - Sealing the cell housing to prevent the electrolyte from being able to leave the cell housing.

[0258] In the context of this aspect of the disclosure: (i) the silicon anode; (ii) the separator; (iii) the cathode; (iv) the electrolyte may be as described in any preceding aspect or in the specific embodiments above.

[0259] Preferably, the battery cell housing is a pouch. More preferably, the battery cell housing is a laminated aluminum pouch.

[0260] Preferably, the step of sealing the battery cell housing is performed in a dry atmosphere. More preferably, the step of sealing the battery cell housing is performed under an inert atmosphere. As non-limiting examples, such an inert atmosphere may be nitrogen or argon.

[0261] The lithium ion battery cell according to this aspect of the disclosure surprisingly has excellent cycle life and capacity.

[0262] Method for forming a solid electrolyte interface layer in a lithium-ion battery cell

[0263] Another aspect of the present disclosure relates to a method of forming a solid electrolyte interface layer in a lithium ion battery cell according to any of the foregoing aspects or embodiments, the method comprising the following steps in the following order:

[0264] (i) providing a lithium ion battery cell according to any preceding claim;

[0265] (ii) charged to at least 4.0 V;

[0266] (iii) Discharge to 3.0V.

[0267] Preferably, the method comprises the following steps in the following order:

[0268] (i) providing a lithium ion battery cell according to any preceding claim; (ii) charging to at least 4.2 V;

[0269] (iii) Discharge to 2.5V.

[0270] More preferably, the method comprises the following steps in the following order:

[0271] (i) providing a lithium-ion battery cell according to any preceding aspect or embodiment; (ii) charging to at least 4.2V;

[0272] (iii) Discharge to 2.5 V;

[0273] (iv) Charge to at least 4.2V.

[0274] Even more preferably, the method comprises the following steps in the following order:

[0275] (i) providing a lithium-ion battery cell according to any preceding aspect or embodiment; (ii) charging to at least 4.2V;

[0276] (iii) Discharge to 2.5 V;

[0277] (iv) charged to at least 4.2 V;

[0278] (v) Discharge to 2.5V.

[0279] More preferably, the method comprises the following steps in the following order:

[0280] (i) providing a lithium-ion battery cell according to any preceding aspect or embodiment; (ii) charging to at least 4.2V;

[0281] (iii) Discharge to 2.5 V;

[0282] (iv) charged to at least 4.2 V;

[0283] (v) Discharge to 2.5 V;

[0284] (vi) Charge to at least 4.2V.

[0285] Preferably, the first charging step to at least 4.0 V, more preferably 4.2 V comprises: - charging at a rate of 0.001 C to 0.1 C for between 1 hour and 24 hours; and - optionally, increasing the charging rate to 0.1 C until 4.2 is reached.

[0286] More preferably, the first charge to at least 4.0V, still more preferably 4.2V comprises:

[0287] - Charge at a rate of 0.002C to 0.05C for between 2 hours and 18 hours; and

[0288] - Optionally, increase the charge rate to 0.1C until 4.2V is reached.

[0289] More preferably, the first charge to at least 4.0V, even more preferably 4.2V comprises:

[0290] - Charge at a rate of 0.005C to 0.02C for between 4 hours and 12 hours; and

[0291] Optionally, increase the charge rate to 0.1C until 4.2V is reached.

[0292] Even more preferably, the first charge to at least 4.2V comprises:

[0293] - Charge at a rate of 0.01C for between 6 hours and 10 hours; and

[0294] Increase the charge rate to 0.1C until 4.2V is reached.

[0295] Preferably, the first discharge to 3.0V, more preferably 2.5V is at 0.02C to 0.2C, more preferably at 0.05C to 0.15C, even more preferably at 0.08C to 0.12C, and most preferably at 0.1C.

[0296] Preferably, the second charge to at least 4.0V, more preferably 4.2V is at 0.05C to 0.4C, more preferably at 0.1C to 0.3C, even more preferably at 0.15C to 0.25C, and most preferably at 0.2C.

[0297] Preferably, the second discharge to 3.0V, more preferably to 2.5V is at 0.05C to 0.4C, more preferably at 0.1C to 0.3C, even more preferably at 0.15C to 0.25C, and most preferably at 0.2C.

[0298] Preferably, the third charge to at least 4.0V, more preferably 4.2V is at 0.05C to 0.4C, more preferably at 0.1C to 0.3C, even more preferably at 0.15C to 0.25C, and most preferably at 0.2C.

[0299] Particularly preferred embodiments of this aspect of the present disclosure relate to a method of forming a solid electrolyte interface layer in a lithium ion battery cell according to any of the preceding aspects or embodiments, the method comprising the following steps in the following order:

[0300] (i) providing a lithium-ion battery cell according to any one of claims 1 to 7;

[0301] (ii) charging at 0.01C for 10 hours;

[0302] (iii) charging at 0.1C for (i) 9 hours or (ii) until the battery reaches 4.2V;

[0303] (iv) Discharge at 0.1C until reaching 2.5V;

[0304] (v) charging at 0.2C until reaching 4.2V;

[0305] (vi) Discharge at 0.2C until reaching 2.5V;

[0306] (vii) Charge at 0.2C for 90 minutes.

[0307] The lithium ion battery cell according to this aspect of the disclosure surprisingly has excellent cycle life and current density.

[0308] Production by process

[0309] Another aspect of the present disclosure relates to a lithium-ion battery cell obtainable by the process as described above. The lithium-ion battery cell according to this aspect of the present disclosure surprisingly has excellent cycle life and capacity.

[0310] Lithium-ion battery cell including a silicon anode containing native voids and a solid electrolyte interface layer

[0311] Another aspect of the present disclosure relates to a lithium-ion battery cell comprising:

[0312] - a silicon anode, the silicon anode comprising:

[0313] i. current collector layer;

[0314] ii. a silicon layer on the current collector layer; and

[0315] iii. Solid electrolyte interface layer,

[0316] The silicon layer includes:

[0317] i. Multiple columnar structures on the current collector;

[0318] ii. a primary void having a width of 1 μm to 10 μm; and

[0319] iii. Optionally, a secondary void having a width of 10 nm to 150 nm;

[0320] -cathode;

[0321] - partitions; and

[0322] - an electrolyte comprising:

[0323] i. lithium salts;

[0324] ii. non-aqueous solvent; and

[0325] iii. diluent.

[0326] The lithium ion battery cell according to this aspect of the disclosure surprisingly has excellent cycle life and current density.

[0327] The current collector and the plurality of columnar structures on the current collector are as described above with respect to the first aspect and other aspects of the present disclosure.

[0328] Native void

[0329] In the context of the present disclosure, the term "native voids" or "native void structures" means areas in the silicon layer that do not contain components of the composite electrode (such as the silicon layer or the SEI layer). The native voids are preferably filled with electrolyte. Without being limited by theory, it is believed that the native voids provide space that allows silicon to expand into it during use of the composite electrode material (parallel to the surface of the collector layer), reducing the amount of cracking, ablation or delamination of the silicon layer. It is further believed that during the use of the lithium-ion battery cell, electrolyte can be present in the native void space, thereby increasing the surface area available for transfer of lithium ions. Typically, such native voids only appear after cycling and / or use of the lithium-ion battery cell.

[0330] Preferably, the primary voids have a width of 2 μm to 9 μm, more preferably 3 μm to 8 μm, even more preferably 4 μm to 6 μm, most preferably 5 μm.

[0331] Preferably, the native voids have an orientation substantially perpendicular to the surface plane of the current collector material. The orientation can be determined from a cross-sectional electron microscope image perpendicular to the surface plane of the current collector material. Determination of the size of the native voids or native void structures can be performed by analyzing a cross-sectional or top-down image of an anode material layer with a SOC of 0% by electron microscopy, wherein the cross section is perpendicular to the surface plane of the current collector layer. Preferably, the width of the native voids or native void structures is determined over a continuous area of ​​the void space or structure by analyzing a cross-sectional image of the layer or material.

[0332] In this context, width means parallel to the surface of the current collector at half the height of the silicon layer.

[0333] The height of silicon is the average height of the silicon pillars measured perpendicular to the surface of the current collector layer.

[0334] Secondary voids

[0335] In the context of the present disclosure, the term "secondary voids" or "secondary void structures" means regions of the silicon layer that are less than 10 nm in width that do not contain components of the composite electrode (such as the silicon layer or the SEI layer). Without being limited by theory, it is believed that the secondary voids provide space that allows silicon to expand into during use of the composite electrode material (parallel to the surface of the current collector layer), reducing the amount of cracking, ablation, or delamination of the silicon layer.

[0336] Preferably, the secondary voids have a width of 20 nm to 140 nm, more preferably 30 nm to 130 nm, even more preferably 40 nm to 120 nm, even more preferably 50 nm to 110 nm, still more preferably 60 nm to 100 nm, most preferably 70 nm to 90 nm.

[0337] Preferably, the secondary voids have an orientation substantially perpendicular to the surface plane of the current collector material. The orientation can be determined from a cross-sectional electron microscope image perpendicular to the surface plane of the current collector material. Preferably, the secondary void structure surrounds the outer curved surface of each of the plurality of columnar structures. Preferably, the secondary void structure extends from the bottom to the top of the corresponding silicon layer and preferably continuously surrounds the columnar structure, thereby defining a separate columnar structure.

[0338] The determination of the size of the secondary voids or primary void structures can be performed by analyzing a cross-sectional image of the anode material layer with a SOC of 0% by electron microscopy, wherein the cross section is perpendicular to the surface plane of the collector layer. Preferably, the width of the primary voids or primary void structures is determined over a continuous area of ​​the void space or structure by analyzing the cross-sectional image of the layer or material.

[0339] In this context, width means parallel to the surface of the current collector at half the height of the silicon layer.

[0340] The height of silicon is the average height of the silicon pillars measured perpendicular to the surface of the current collector layer.

[0341] Solid electrolyte interface layer

[0342] This may be any solid electrolyte interfacial layer formed by charging and discharging the anode in the presence of a lithium salt containing electrolyte.

[0343] Preferably, according to any embodiment of the first aspect of the present disclosure, the solid electrolyte interface layer is formed by charging and discharging the anode in the presence of an electrolyte.

[0344] Battery

[0345] In yet another aspect, the present disclosure relates to a battery comprising at least one lithium-ion battery cell according to any of the foregoing embodiments of any of the foregoing aspects. An advantage of such a battery is that the mass of such a battery can be lower than that of the prior art while still having the same nominal voltage and capacity. In the context of the present disclosure, a battery may comprise one or more lithium-ion battery cells.

[0346] Battery shape

[0347] Examples of such batteries are cylindrical batteries, prismatic batteries, pouch batteries, and coin batteries. Several configurations of lithium-ion battery cells can also be combined. For example, a coin cell can have an internal cylindrical configuration (as disclosed in international patent application WO2015188959A1), or a pouch cell can have an internal prismatic configuration.

[0348] Typically, lithium-ion secondary batteries are manufactured as follows. First, a positive electrode and a negative electrode are provided. Subsequently, in order to manufacture a battery cell having a predetermined shape, a plurality of positive electrode plates and a plurality of negative electrode plates are stacked in a state where a separator is sandwiched between the positive electrode plate and the negative electrode plate, respectively. Subsequently, the battery cell is placed in a battery housing, and an electrolyte is provided to the battery housing. The battery housing is then typically sealed, thereby producing a battery, such as a battery pack.

[0349] The electrode lead is connected to the common electrode assembly. Each electrode lead is configured to have a structure in which one end of the electrode lead is connected to the electrode assembly, the other end of the electrode lead is exposed to the outside of the battery case, and the battery case in which the electrode assembly is placed is sealed by an adhesive layer such as a sealant layer at a portion of the battery case where the electrode lead extends outward from the battery case.

[0350] In addition, the electrode assembly is provided with an electrode tab. Each collector plate of the electrode assembly includes a coated portion coated with an electrode active material and an end portion (hereinafter referred to as a "non-coated portion") that may not be coated with an electrode active material. Each electrode tab can be formed by connecting an uncoated portion, or preferably by connecting a separate conductive tab connected to the electrode, and even more preferably by ultrasonic welding. These electrode tabs may protrude in one direction so that the electrode tabs are formed at the electrode assembly in a side-by-side arrangement. Alternatively, the electrode tabs may protrude in opposite directions. Each electrode tab is then conveniently used as a path for electrons to move between the inside and outside of the battery. In addition, each electrode lead is preferably connected to the corresponding electrode tab by spot welding.

[0351] The electrode leads may extend in the same direction or in opposite directions, depending on where the positive electrode tab and the negative electrode tab are formed. The positive electrode lead and the negative electrode lead may be made of different materials. Finally, the electrode lead is electrically connected to an external terminal via its terminal portion.

[0352] The bag-like sheath member includes an electrode assembly in a sealed state so that a portion of each electrode lead (e.g., a terminal portion of each electrode lead) is exposed from the bag-like sheath member. As previously described, an adhesive layer (such as a sealant layer) is sandwiched between each electrode lead and the bag-like sheath member. The bag-like sheath member is provided with a sealing area at its edge. The horizontal slit of each electrode lead is spaced apart from the sealing area toward the joint. That is, when each electrode lead is formed to have an inverted T-shape, the legs of the T-shape protrude outward from the bag-like sheath member, and a portion of the head of the T-shape is located in the sealing area.

[0353] Prismatic battery

[0354] In a preferred embodiment, the battery is approximately rectangular in shape with a height of 48.5 mm, a length of 26.5 mm and a width of 17.5 mm. Preferably, the battery has a nominal voltage of 9 volts. Preferably, the battery is rechargeable.

[0355] In another embodiment, the present disclosure relates to a rectangular battery comprising a battery cell according to any of the preceding embodiments of any of the preceding aspects. Preferably, the rectangular battery is selected from: a 4.5 volt lantern battery, a 6 volt (spring or screw fitting) lantern battery; a 7.5 volt lantern battery; a 12 volt lantern battery; or a 9 volt battery.

[0356] Cylindrical battery

[0357] A cylindrical lithium-ion secondary battery typically comprises a spirally wound electrode assembly comprising a cathode and an anode between which a separator is spirally wound, and a pair of insulating plates in a substantially hollow cylindrical battery can. In a preferred embodiment, the battery is a cylindrical battery having a diameter of 17 mm and a height of 34.5 mm. Preferably, the battery has a nominal voltage of 3.6 volts. More preferably, the battery has a nominal voltage of 3.6 volts and a capacity of 700 mAh. Preferably, the battery is rechargeable.

[0358] In a preferred embodiment, the battery has a cylindrical shape with a diameter of 15.6 mm and a length of 27 mm. Preferably, the battery has a nominal voltage of 3.6 volts. More preferably, the battery has a nominal voltage of 3.6 volts and a capacity of 600 mAh or 800 mAh. Preferably, the battery is rechargeable.

[0359] In a preferred embodiment, the battery is a cylindrical battery with a diameter of 17 mm and a height of 34.5 mm. Preferably, the battery has a nominal voltage of 3.6 volts. More preferably, the battery has a nominal voltage of 3.6 volts and a capacity of 700 mAh.

[0360] Double cylindrical battery

[0361] In a preferred embodiment, the battery has a dual cylindrical shape with a height of 52.20 mm, a length of 28.05 mm, and a width of 14.15 mm. More preferably, the battery has a nominal voltage of 3.6 volts and a capacity of 1300 mAh.

[0362] Button battery

[0363] Button cells are also commonly referred to as coin cells, which are thin compared to their diameter. In a preferred embodiment, the battery is a button cell having a diameter of 9.5 mm and a height of 2.7 mm. Preferably, the battery has a nominal voltage in the range of 2.8 volts to 4.0 volts, preferably 3.0 volts to 3.8 volts, preferably 3.2 volts to 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.3 volts, 3.4 volts, 3.5 volts or 3.6 volts, and a capacity of 30 mAh for continuous discharge to 2.0 volts per cell.

[0364] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 10 mm and a height of 2.5 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 30 mAh for continuous discharge to 2.0 volts per cell.

[0365] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 11.5 mm and a height of 3.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 70 mAh for continuous discharge to 2.0 volts per cell.

[0366] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 11 mm and a height of 10.8 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 160 mAh for continuous discharge to 2.0 volts per cell.

[0367] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 12.5 mm and a height of 1.6 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 25 mAh for continuous discharge to 2.0 volts per cell.

[0368] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 12.5 mm and a height of 2.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 35 mAh to 40 mAh for continuous discharge to 2.0 volts per cell.

[0369] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 12.5 mm and a height of 2.5 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 50 mAh for continuous discharge to 2.0 volts per cell.

[0370] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 16 mm and a height of 1.6 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 50 mAh to 55 mAh for continuous discharge to 2.0 volts per cell.

[0371] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 16 mm and a height of 2.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 75 mAh to 78 mAh for continuous discharge to 2.0 volts per cell.

[0372] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 16 mm and a height of 3.2 mm.

[0373] Preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts.

[0374] More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 140 mAh for continuous discharge to 2.0 volts per cell.

[0375] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 20 mm and a height of 1.2 mm. Preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 55 mAh for continuous discharge to 2.0 volts per cell.

[0376] In a preferred embodiment, the battery is a button-shaped cell with a diameter of 20 mm and a height of 1.6 mm. Preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts and a capacity of 90 mAh for continuous discharge to 2.0 volts per cell. In a preferred embodiment, the battery is a button-shaped cell with a diameter of 20 mm and a height of 2.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts. More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 115 mAh to 125 mAh for continuous discharge to 2.0 volts per cell.

[0377] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 20 mm and a height of 2.5 mm. Preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 160 mAh to 165 mAh for continuous discharge to 2.0 volts per cell.

[0378] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 20 mm and a height of 3.2 mm. Preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 225 mAh for continuous discharge to 2.0 volts per cell. Preferably, the battery has a maximum discharge current of 3 mA. Preferably, the battery has a maximum pulse discharge current of 15 mA. Preferably, the battery has a mass of less than 3.0 g, more preferably less than 2.9 g, even more preferably less than 2.8 g.

[0379] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 20 mm and a height of 4.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 280 mAh for continuous discharge to 2.0 volts per cell.

[0380] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 23 mm and a height of 2.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 350 mAh for continuous discharge to 2.0 volts per cell.

[0381] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 23 mm and a height of 2.0 mm. Preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 110 mAh to 175 mAh for continuous discharge to 2.0 volts per cell.

[0382] In a preferred embodiment, the battery is a button-shaped battery with a diameter of 23 mm and a height of 2.5 mm. Preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 165 mAh to 210 mAh for continuous discharge to 2.0 volts per cell. In a preferred embodiment, the battery is a button-shaped battery with a diameter of 23 mm and a height of 3.0 mm.

[0383] Preferably, the battery has a nominal voltage of 3.0 V or 3.2 V, 3.4 V or 3.6 V. More preferably, the battery has a nominal voltage of 3.0 V or 3.2 V, 3.4 V or 3.6 V, and a capacity of 265 mAh for continuous discharge to 2.0 V per cell.

[0384] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 23 mm and a height of 3.5 mm. Preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts, or 3.6 volts, and a capacity of 165 mAh for continuous discharge to 2.0 volts per cell.

[0385] In a preferred embodiment, the battery is a button-shaped battery with a diameter of 23 mm and a height of 5.4 mm. Preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 560 mAh for continuous discharge to 2.0 volts per battery cell. In a preferred embodiment, the battery is a button-shaped battery with a diameter of 24 mm and a height of 1.2 mm. Preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 100 mAh for continuous discharge to 2.0 volts per battery cell. In a preferred embodiment, the battery is a button-shaped battery with a diameter of 24 mm and a height of 3.0 mm. Preferably, the battery has a nominal voltage of 3.0 V or 3.2 V, 3.4 V or 3.6 V. More preferably, the battery has a nominal voltage of 3.0 V or 3.2 V, 3.4 V or 3.6 V, and a capacity of 270 mAh to 290 mAh for continuous discharge to 2.0 V per cell.

[0386] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 24 mm and a height of 5.0 mm. Preferably, the battery has a nominal voltage of 3.0 to 3.8 volts, such as 3.2, 3.4 or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 or 3.2 volts and a capacity of 610 to 620 mAh for continuous discharge to 2.0 volts per cell.

[0387] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 24 mm and a height of 7.7 mm. Preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 1000 mAh for continuous discharge to 2.0 volts per cell. In a preferred embodiment, the battery is a button-shaped battery having a diameter of 26.2 mm and a height of 1.67 mm.

[0388] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 30 mm and a height of 3.2 mm.

[0389] Preferably, the battery has a nominal voltage of 3.0 V or 3.2 V, 3.4 V or 3.6 V. More preferably, the battery has a nominal voltage of 3.0 V or 3.2 V, 3.4 V or 3.6 V, and a capacity of 500 mAh to 560 mAh for continuous discharge to 2.0 V per cell.

[0390] In a preferred embodiment, the battery is a button-shaped battery having a diameter of 30 mm and a height of 3.2 mm. Preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts. More preferably, the battery has a nominal voltage of 3.0 volts or 3.2 volts, 3.4 volts or 3.6 volts, and a capacity of 500 mAh to 560 mAh for continuous discharge to 2.0 volts per cell.

[0391] Flat or bag-shaped

[0392] The design of a single cell around a high energy positive electrode active material can provide a battery with high capacity within a practical form factor. Pouch cells are typically approximately rectangular, excluding connection tabs and other potential features around the edges, and are characterized by a thickness (t) and a planar area having a width (w) and a height (h), wherein the thickness is typically significantly smaller than the linear dimensions (width and height) defining the planar area (w·h), such as Figure 2 In particular, the battery may have a thickness between about 7 mm and about 18 mm. The area of ​​the pouch cell may be in the range of about 25,000 mm2 to about 50,000 mm2, wherein the linear dimensions of the width and height defining the area are typically in the range of about 50 mm to about 750 mm.

[0393] When discharged from 4.5V to 2.0V, the resulting single cell can typically have a discharge energy density of at least about 160Wh / kg. In some advantageous embodiments, when discharged from 4.5V to 2.0V, the resulting battery can have a discharge energy density of at least about 200Wh / kg, and in other embodiments, about 250Wh / kg to about 400Wh / kg. In other embodiments, the battery can have a volumetric discharge energy density of at least about 300Wh / l. In other advantageous embodiments, when discharged from 4.5V to 2.0V, the resulting battery can have a volumetric discharge energy density of at least about 500Wh / l to 1150Wh / l.

[0394] In the above embodiments, a battery of a prismatic, cylindrical, laminated film, coin or button type or spirally wound configuration is described. However, the battery according to the present invention can be applied to any other shape, wherein the battery element has any other configuration such as a laminated configuration.

[0395] Use of a battery cell or battery according to any preceding aspect

[0396] Another aspect of the present disclosure is the use of a battery cell or battery according to any preceding aspect or embodiment of the present disclosure as an energy storage and / or release device.

[0397] The term "energy storage and / or release device" herein is understood to refer to a secondary battery, including an electrode assembly of a cathode / separator / anode structure mounted in a suitable battery case. Such batteries include lithium-ion secondary batteries, which excel in providing high energy density and high capacity; and their use in secondary battery modules including a plurality of secondary batteries, which are typically connected in series to form a battery pack, which can be incorporated into a housing to form a module.

[0398] Specific electrolytes

[0399] In another aspect, the present disclosure relates to an electrolyte comprising:

[0400] - 9 to 29 wt.% of lithium bis(fluorosulfonyl)imide;

[0401] -1,2-dimethoxyethane; and

[0402] -1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether,

[0403] The electrolyte has a molar ratio of (lithium bis(fluorosulfonyl)imide):(1,2-dimethoxyethane):(1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether) of 1:x:y, wherein 1.2≤x≤3.0 and 2.0≤y≤4.0.

[0404] Preferably, wherein 1.2≤x≤2.5 and 2.2≤y≤3.8, more preferably wherein 1.2≤x≤2.0 and 2.4≤y≤3.6, even more preferably wherein 1.2≤x≤1.8 and 2.8≤y≤3.2, most preferably wherein x=1.2 and y=3.0.

[0405] Without being limited by theory, it is believed that the electrolyte according to the present invention has advantageous electrolyte properties, enabling lithium ion battery cells including such electrolytes to achieve longer cycle life.

[0406] Detailed description of the drawings

[0407] The present disclosure will now be discussed with reference to the accompanying drawings, which show preferred exemplary embodiments of the present disclosure.

[0408] Figure 1 A conventional silicon anode material is schematically depicted in a first unlithiated state (top), a fully lithiated state (middle), and a fully delithiated state (bottom).

[0409] Figure 2 Schematic depiction of a conventional silicon anode material during SEI formation, in a first unlithiated state (top), a fully lithiated state (middle), and a fully delithiated state (bottom).

[0410] Figure 3 A schematic depiction of a silicon anode material wherein the silicon layer comprises a plurality of pillar-like structures on a current collector. It depicts the silicon anode material in a first unlithiated state (top), a fully lithiated state (middle), and a fully delithiated state (bottom).

[0411] Figure 4 A schematic depiction of a silicon anode material, wherein the silicon layer includes (i) a plurality of columnar structures on a current collector and (ii) a SEI. It depicts the silicon anode material in a first unlithiated state (top), a fully lithiated state (middle), and a fully delithiated state (bottom).

[0412] Figure 5 Schematically depicts a silicon anode material in a lithium battery cell according to the present invention. It depicts the silicon anode in a first unlithiated state (top), a fully lithiated state (middle) and a fully delithiated state (bottom).

[0413] Fig. 6A is a top-down scanning electron microscope image obtained from an anode including a silicon layer, where the silicon layer includes a plurality of columnar structures.

[0414] Figure 6B is a cross-sectional scanning electron microscope image obtained from an anode including a silicon layer, wherein the silicon layer includes a plurality of columnar structures.

[0415] Fig. 7A is the area capacity (mAh / cm 2 ) is a graph of the number of cycles experimentally obtained for materials according to the present disclosure (Example 3) and the comparative example (Example 3A).

[0416] Figure 7B is a graph of capacity retention (%) versus the number of cycles experimentally obtained for materials according to the present disclosure (Example 3) and a comparative example (Example 3A).

[0417] Figure 7C is a graph of cumulative specific capacity (Ah / g) versus number of cycles experimentally obtained for materials according to the present disclosure (Example 3, straight solid line) and comparative examples (Example 3A, curved solid line).

[0418] Fig. 8A is a graph of capacity retention (%) versus number of cycles experimentally obtained for materials according to the present disclosure (Example 6, top line) and comparative examples (Example 6A, curved solid line).

[0419] Figure 8Bis a graph of Coulombic efficiency (%) versus number of cycles experimentally obtained for materials according to the present disclosure (Example 6, top line) and the comparative example (Example 6A, bottom line).

[0420] Fig.9A 3 (left) and Comparative Example 3A (right) after performing Method 6 at 0% state of charge. It can be seen that the surface morphology of the anode of the lithium-ion battery cell according to the present disclosure is significantly different from the surface morphology of the lithium-ion battery cell made using conventional carbonate-based electrolytes. After performing the methods of Example 6 and Example 6A, the surface morphology of both the lithium-ion battery cell according to the present disclosure and the lithium-ion battery cell made using conventional carbonate-based electrolytes is characterized by columnar silicon islands separated by cracks. These are visually reminiscent of mud-cracks.

[0421] Fig. 9B 3 (left) and Comparative Example 3A (right) after performing Method 6 at 50% state of charge. It can be seen that the surface morphology of the anode of the lithium-ion battery cell according to the present disclosure is significantly different from the surface morphology of the lithium-ion battery cell made using a conventional carbonate-based electrolyte. After performing the methods of Example 6 and Example 6A, the surface morphology of both the lithium-ion battery cell according to the present disclosure and the lithium-ion battery cell made using a conventional carbonate-based electrolyte is characterized by columnar silicon islands separated by cracks. These are visually reminiscent of dry cracks.

[0422] List of reference numerals

[0423] 1 Silicon anode

[0424] 2. Current collector layer

[0425] 3 Silicon layer

[0426] 4 Cracks in the silicon layer

[0427] 5. Ablated silicon (broken silicon)

[0428] 6 Layered Silicon

[0429] 7Solid Electrolyte Interface (SEI) Layer

[0430] 8SEI and cracks in the silicon layer

[0431] 9 Ablated SEI and Silicon

[0432] 10 Layers of Silicon

[0433] 11 Ablated SEI

[0434] 12 Columnar structure

[0435] 13 Excessive SEI deposition

[0436] 14SEI is layered from the inside of the columnar structure wall

[0437] 15 SEI delamination from the top of the columnar structure

[0438] 16 Ablation of SEI from the top of the columnar structure

[0439] 17 Ablation of SEI from the columnar structure wall

[0440] 18 Columnar structure islands of silicon connected by SEI

[0441] 19 Secondary void

[0442] 20 Native Gap

[0443] aDirection of the force exerted by the swelling of silicon

[0444] b The structure avoids the direction in which force is applied.

[0445] Example

[0446] The following non-limiting examples illustrate products and processes according to the present disclosure.

[0447] Example 1 - Preparation of an Electrolyte Solution According to the Disclosure

[0448] The lithium salt lithium bis(fluorosulfonyl)imide (187 g, 1.0 mole) was added to the non-aqueous solvent 1,2-dimethoxyethane (108 g, 1.2 mole mol) at 22° C. with continuous stirring. Once all the lithium salt was completely dissolved, the diluent 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (696 g, 3.0 mole) was added with further stirring at 22° C. The resulting electrolyte was evaluated and showed favorable electrolyte properties.

[0449] Example 2 - Preparation of anode material [silicon with columnar morphology at the nanoscale]

[0450] A roll of roughened copper foil current collector material (Sa 0.51 μm, Sq 0.65 μm, Sz 5.9 μm, Sds 0.77 μm) was placed on the -2, SSC 16.2μm-2, SDQ 2.1μm, Sdr 157%, as determined by standard method ISO 25178) is fed into a plasma enhanced chemical vapor deposition (PECVD) device, which includes an unwinding chamber, two deposition chambers and a rewinding chamber. These chambers are all connected and usually operate under vacuum (0.05-0.2 mbar). The foil is transported by a tension roller system and two heating drums that control the temperature of the foil. At a substrate temperature of 100°C to 300°C, the first silicon layer is deposited by PECVD onto the same side of the copper substrate. In this process, magnetron radiation with a frequency of 2.45GHz is used to excite a gas mixture containing a silicon precursor gas and a supporting gas. Silane (SiH4) is the source of silicon, while argon (Ar) and hydrogen (H2) are added to stabilize the plasma, affect the material structure and increase the deposition rate. The gas is injected via a "gas shower" that evenly distributes the gas.

[0451] Magnetron (microwave) radiation is introduced into the vacuum chamber with the aid of an antenna. To ensure a uniform plasma, both sides of the antenna are connected to a source of magnetron radiation. Magnetron heads are therefore located on each side of the antenna. These magnetron heads are connected to the antenna. Gas is injected via a gas shower close to the magnetron heads. The antenna is protected from the reaction environment by a quartz tube. The plasma is confined by a magnetic field generated by an array of permanent magnets.

[0452] The silicon production rate is determined by the process conditions, the power input to each source and the number of microwave sources in operation. The gas flow rate is proportional to the MW power input, which is 800W / m-6000W / m. Ten antennas or power inputs are used.

[0453] Fig. 6A is a top-down scanning electron microscope (SEM) image of the obtained material. Figure 6B is a cross-sectional scanning electron microscope (SEM) image of the obtained material. The bar represents 10 μm, and each scale corresponds to 1 μm.

[0454] Cross-sectional SEM ( Figure 6B ) determined that the deposited silicon layer had a thickness of 8 to 9 μm. BET analysis determined that the material had a surface area of ​​79.9 m 2 / g, the porosity is 15.73%, and the average pore size is 4.01nm. XRF analysis shows that the mass loading is 1.27mg / cm 2 -1.29mg / cm 2 The deposited material had a CIELAB lightness value L* of 42.07 to 42.98.

[0455] Example 3 - Preparation of a pouch-type lithium-ion battery cell according to the present disclosure

[0456] A pouch cell was constructed by stacking (i) anode material as prepared above [Example 2], (ii) a ceramic coated separator (12 μm polymer polypropylene coated on both sides with 2 μm alumina layers from Gelon LIB Group, China), and (iii) a cathode material (3.5 mAh / cm 2 Lithium nickel manganese cobalt oxide NMC 622, commercially available from CUSTOMCELLS). Both the cathode and anode are connected to an external circuit via electrode tabs, which are welded to the electrodes by conventional methods. The tabbed and stacked cells are bagged in a commercially available laminated aluminum bag material, which is sealed on three sides. The electrolyte prepared according to Example 1 is added to the laminated aluminum bag under a dry atmosphere and then vacuum sealed.

[0457] Comparative Example 3A - Preparation of a conventional pouch-type lithium-ion battery cell

[0458] A pouch cell was constructed by stacking: (i) an anode material prepared as in [Example 2] above, (ii) a ceramic separator using a 12 μm polymer polypropylene film coated on both sides with a 2 μm alumina layer from Gelon LIB Group, China; and (iii) a cathode material using a 3.5 mAh / cm 2 The lithium nickel manganese cobalt oxide NMC 622 anode is used as the cathode material. Both the cathode and the anode are connected to the external circuit by electrode tabs, which are welded to the electrodes by conventional methods. The cells with tabs and stacks are bagged in a laminated aluminum bag material, which is sealed on three sides. A commercially available electrolyte is added to the laminated aluminum bag under a dry atmosphere and then vacuum sealed. The electrolyte of commercial origin is a solution of LiPF6 (1M) in a mixture of 1,3-dioxolane-2-one (ethylene carbonate, EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, the mixture additionally containing 5wt.% of fluoroethylene carbonate, 2wt.% of vinyl carbonate and 2wt.% of adiponitrile (AN).

[0459] Example 4 - Cycle Life / Capacity Retention Analysis

[0460] The battery cells according to the present disclosure prepared according to Example 3 and the comparative battery cells prepared according to Example 3A were evaluated for their capacity retention properties.

[0461] The cycling conditions used were C / 2 rate, 3 V to 4.2 V at 25°C (constant voltage [CV] steps at 4.2 V up to C / 20 rate).

[0462] exist Fig. 7A , Figure 7B and Figure 7CThe results are presented in .

[0463] The results show that the lithium-ion battery cell according to the present disclosure shows that the lithium-ion battery cell according to the present disclosure:

[0464] - Maintains high areal capacity over significantly more charge cycles than comparative examples;

[0465] - Maintains high capacity retention over significantly more charge cycles than the comparative examples; and

[0466] - Maintaining a substantially linear cumulative specific capacity relationship for significantly more charging cycles, and maintaining a higher cumulative specific capacity up to a lifetime capacity onset value of 80%.

[0467] Thus, the lithium-ion battery cells according to the present disclosure exhibit improved capacity retention, and therefore improved cycle life, compared to lithium-ion battery cells made using conventional carbonate-based electrolytes. For lithium-ion battery cells according to the present disclosure, the number of cycles required for the cumulative specific capacity to drop to 80% of the life capacity starting value is approximately twice that of lithium-ion battery cells made using conventional carbonate-based electrolytes, where the cumulative specific capacity is a measure of how much capacity is normalized to the mass of silicon.

[0468] Example 5 - Cycle Life / Capacity Retention Analysis without Constant Voltage Step

[0469] The lithium ion battery cells according to the present disclosure prepared according to Example 3 and the comparative lithium ion battery cells prepared according to Example 3A were evaluated for their capacity retention properties.

[0470] The cycling conditions used were C / 2 rate, 3 V to 4.2 V at 25°C.

[0471] exist Fig. 8A The results are presented in Fig. 8A It can be seen that the lithium-ion battery cell according to the present disclosure can experience about 200 cycles before the capacity retention rate drops to 93%, while the lithium-ion battery cell made using a conventional carbonate-based electrolyte can only experience about 50 cycles before the capacity retention rate drops to 93%. Figure 8B It is shown that lithium-ion battery cells according to the present disclosure achieve higher coulombic efficiency (>99.9%), while lithium-ion battery cells made using conventional carbonate-based electrolytes only achieve a maximum of 99.8%.

[0472] The results show that the lithium-ion battery cell according to the present disclosure:

[0473] - Shows better capacity retention than lithium-ion battery cells made with conventional carbonate-based electrolytes; and

[0474] -Have higher Coulombic efficiency (approximately >99.9%) than lithium-ion battery cells made with conventional carbonate-based electrolytes (approximately 99.8%).

[0475] The higher coulombic efficiency indicates that the lithium-ion battery cells according to the present disclosure experience less side reactions and lithium inventory losses compared to lithium-ion battery cells made using conventional carbonate-based electrolytes.

[0476] Example 6 - Solid Electrolyte Interface Formation Method According to the Present Disclosure

[0477] A lithium-ion battery cell was prepared according to Example 3, and the following steps were performed:

[0478] - Rest for 1 hour;

[0479] -0.01C charging for 10 hours;

[0480] - 0.1C charge for (i) 9 hours or (ii) until reaching 4.2V;

[0481] - Rest for 30 minutes;

[0482] -0.1C discharge until reaching 2.5V;

[0483] - Rest for 30 minutes;

[0484] -0.2C charge until reaching 4.2V;

[0485] - Rest for 30 minutes;

[0486] -0.2C discharge until reaching 2.5V;

[0487] -Rest for 30 minutes.

[0488] The solid electrolyte interface is formed during the formation of the lithium-ion battery cell held in a pressure clamp (about 350 psi at the initial state).

[0489] Example 6A - Solid Electrolyte Interface Formation Method According to the Present Disclosure

[0490] A lithium-ion battery cell was prepared according to Example 3A, and the following steps were performed:

[0491] - Rest for 1 hour;

[0492] -0.01C charging for 10 hours;

[0493] - 0.1C charge for (i) 9 hours or (ii) until reaching 4.2V;

[0494] - Rest for 30 minutes;

[0495] -0.1C discharge until reaching 2.5V;

[0496] - Rest for 30 minutes;

[0497] -0.2C charge until reaching 4.2V;

[0498] - Rest for 30 minutes;

[0499] -0.2C discharge until reaching 2.5V;

[0500] -Rest for 30 minutes.

[0501] The solid electrolyte interface was formed in a lithium-ion battery cell held in a pressure clamp (about 350 psi at the initial state).

[0502] Example 7 - Analysis of anode surface morphology after charge cycle and full discharge

[0503] The lithium ion battery cells according to the present disclosure prepared according to Example 3 and the comparative lithium ion battery cells prepared according to Example 3A were evaluated for their morphological properties after formation (full cycle ended in a discharged state).

[0504] The cycling conditions used were those of Example 6A, ending at 2.5 V and 0% state of charge (SOC).

[0505] The lithium-ion battery cells were then disassembled under inert conditions and analyzed by scanning electron microscopy (SEM). Representative SEM images are reproduced from Fig.9A As can be seen, the surface morphology of the anode of the lithium-ion battery cell according to the present disclosure is significantly different from the surface morphology of the lithium-ion battery cell made using a conventional carbonate-based electrolyte. After performing the methods of Example 6 and Example 6A, the surface morphology of both the lithium-ion battery cell according to the present disclosure and the lithium-ion battery cell made using a conventional carbonate-based electrolyte is characterized by columnar silicon islands separated by cracks. These are visually reminiscent of dry cracks.

[0506] After performing the method of Example 6 or Comparative Example 6A, the surface morphology of the lithium-ion battery cell according to the present disclosure is unexpectedly different from the surface morphology of the lithium-ion battery cell made using a conventional carbonate-based electrolyte in that the crack density is significantly lower, the islands are significantly larger, and the cracks are significantly wider.

[0507] The exact mechanism that allows morphological control of the anode surface by the disclosed electrolyte is unknown.

[0508] Without being limited by theory, it is believed that lithium-ion battery cells exhibiting surface morphology characterized by lower crack density, large islands, and wider cracks unexpectedly allow for lower surface area and therefore less parasitic decomposition of electrolyte, and therefore less solid electrolyte interface formation, and thus contribute to higher cycle life of such lithium-ion battery cells.

[0509] Example 8 - Analysis of anode surface morphology after charge cycling and partial charging

[0510] The lithium ion battery cells according to the present disclosure prepared according to Example 3 and the comparative lithium ion battery cells prepared according to Example 3A were evaluated for their capacity retention properties.

[0511] The loop conditions used are as follows:

[0512] - Rest for 1 hour;

[0513] -0.01C charging for 10 hours;

[0514] - 0.1C charge for (i) 9 hours or (ii) until reaching 4.2V;

[0515] - Rest for 30 minutes;

[0516] -0.1C discharge until reaching 2.5V;

[0517] - Rest for 30 minutes;

[0518] -0.2C charge until reaching 4.2V;

[0519] - Rest for 30 minutes;

[0520] -0.2C discharge until reaching 2.5V;

[0521] Ends at 2.5V

[0522] - Rest for 30 minutes

[0523] -0.2C charging until 50% state of charge (SOC).

[0524] The lithium-ion battery cells were then disassembled under inert conditions and analyzed by scanning electron microscopy (SEM). Representative SEM images are reproduced from Fig. 9B As can be seen, the surface morphology of the anode of the lithium-ion battery cell according to the present disclosure is significantly different from the surface morphology of the lithium-ion battery cell made using a conventional carbonate-based electrolyte. After performing the above method, the surface morphology of both the lithium-ion battery cell according to the present disclosure and the lithium-ion battery cell made using a conventional carbonate-based electrolyte is characterized by columnar silicon islands separated by voids (cracks). These are visually reminiscent of dry cracks.

[0525] After executing the above method, the surface morphology of the lithium-ion battery cell according to the present disclosure is unexpectedly different from the surface morphology of the lithium-ion battery cell made using conventional carbonate-based electrolytes, with the difference being that the void (crack) density is significantly lower, the islands are significantly larger, and the voids (cracks) are significantly wider.

[0526] The exact mechanism that allows morphological control of the anode surface by the disclosed electrolyte is unknown.

[0527] Without being limited by theory, it is believed that lithium-ion battery cells exhibiting surface morphology characterized by lower void (crack) density, large islands, and wider voids (cracks) unexpectedly allow for lower surface area, and therefore less parasitic decomposition of the electrolyte, and therefore less solid electrolyte interface formation, and thus increase the cycle life of such lithium-ion battery cells.

Claims

1. A lithium-ion battery cell, comprising: - a silicon anode, the silicon anode comprising: i. a current collector layer; and ii. Silicon layer, wherein the silicon layer includes a plurality of columnar structures on the current collector; -cathode; - partitions; and - an electrolyte comprising: i. 9 wt.% to 29 wt.% of a lithium salt relative to the electrolyte; ii. a non-aqueous solvent; and iii. diluent, The electrolyte has a lithium salt-solvent-diluent molar ratio of 1:x:y, wherein 1.0≤x≤3.0 and 2.0≤y≤4.

0.

2. The lithium-ion battery cell according to claim 1, wherein: The silicon layer has a depth of 1 μm to 200 μm, preferably 2 μm to 100 μm, more preferably 4 μm to 75 μm, even more preferably 5 μm to 50 μm, and most preferably 5 μm to 30 μm.

3. The lithium-ion battery cell according to claim 1 or claim 2, wherein: The silicon layer comprises: i. a plurality of columnar structures on the current collector, the columnar structures extending mainly in a vertical direction from the surface of the current collector layer; and ii. a native void having a width of 1 μm to 10 μm; and optionally, iii. Secondary voids having a width of 10 nm to 150 nm.

4. The lithium-ion battery cell according to any one of claims 1 to 3, wherein: The electrolyte has a lithium salt-solvent-diluent molar ratio of 1:x:y, wherein 1.1≤x≤2.5 and 2.2≤y≤3.8, more preferably 1.2≤x≤2.0 and 2.4≤y≤3.6, even more preferably 1.2≤x≤1.8 and 2.6≤y≤3.4, and most preferably x=1.2 and y=3.

0.

5. A lithium-ion battery cell according to any preceding claim, wherein: The lithium salt is lithium bis(fluorosulfonyl)imide.

6. A lithium-ion battery cell according to any preceding claim, wherein: i. The non-aqueous solvent is 1,2-dimethoxyethane.

7. A lithium-ion battery cell according to any preceding claim, wherein: i. The diluent is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

8. A lithium-ion battery cell according to any preceding claim, wherein: The silicon layer has a porosity of 0% to 80%, preferably 5%-60%, even more preferably 10%-40%, as determined by the BJH method of ISO 15901-2:2006.

9. A lithium-ion battery cell according to any preceding claim, wherein: The battery cell can be obtained by a process comprising the following steps, which are arranged in the following order: (i) providing a lithium-ion battery cell according to any one of the preceding claims; (ii) charging the battery cell to at least 4.0V; (iii) Discharging the battery cell to 3.0V.

10. A lithium ion battery cell according to any preceding claim, wherein: The battery cell can be obtained by a process comprising the following steps, which are arranged in the following order: (i) providing a lithium-ion battery cell according to any one of claims 1 to 8; (ii) charging at 0.01C for 10 hours; (iii) charging at 0.1C for (i) 9 hours or (ii) until the battery reaches 4.2V; (iv) Discharge at 0.1C until reaching 2.5V; (v) charging at 0.2C until reaching 4.2V; (vi) Discharge at 0.2C until reaching 2.5V; (vii) Charge at 0.2C for 90 minutes.

11. A lithium-ion battery cell comprising: - a silicon anode, the silicon anode comprising: i. current collector layer; ii. a silicon layer on the current collector layer; and iii. Solid electrolyte interface layer, The silicon layer comprises: iv. a plurality of columnar structures on the current collector, wherein the columnar structures mainly extend in a vertical direction from the surface of the current collector layer; v. Optionally, native voids, the native voids having a width of 1 μm to 10 μm; and vi. Optionally, a secondary void, wherein the secondary void has a width of 10 nm to 150 nm; -cathode; - partitions; and - an electrolyte comprising: i. lithium salts; ii. a non-aqueous solvent; and iii. diluent.

12. A lithium ion battery cell according to any preceding claim, wherein: The lithium-ion battery cell is capable of operating at a voltage of 2.5V to 4.6V, more preferably 3.0V to 4.5V, and more preferably 3.2V to 4.2V.

13. A battery comprising a lithium ion battery cell according to any preceding claim.

14. Use of a lithium-ion battery cell according to any one of claims 1 to 11 or a battery according to claim 12 as an energy storage and / or release device.

15. A method of manufacturing a lithium-ion battery cell according to any one of claims 1 to 8.

16. The method according to claim 15, comprising the steps of: (i) providing a lithium ion battery cell according to any preceding claim; (ii) charged to at least 4.0 V; (iii) Discharge to 3.0V.

17. The method of manufacturing a lithium-ion battery cell according to claim 15, further comprising providing: a. Charge at 0.01C for 10 hours; b. Charge at 0.1C for (i) 9 hours or (ii) until it reaches 4.2V; c. Discharge at 0.1C until it reaches 2.5V; d. Charge at 0.2C until it reaches 4.2V; e. Discharge at 0.2C until reaching 2.5V; f. Charge at 0.2C for 90 minutes.

Citation Information

Patent Citations

  • Lithography process optimization and system

    US20070031744A1

  • Localized superconcentrated electrolytes for stable cycling of electrochemical devices

    US20180254524A1

  • Electrode including nanostructures for rechargeable cells

    WO2010129910A2

  • Structurally controlled deposition of silicon onto nanowires

    WO2015175509A1

  • Method for producing a lithium ion cell having a wound structure and cell

    WO2015188959A1